FLEXIBLE POROUS DISSOLVEABLE SOLID SHEET ARTICLE CONTAINING DIRECT-LOAD MICROCAPSULES AND METHODS FOR MAKING SAME - Patent application
Directly adding perfume microcapsules to a wet premix before aeration and drying in flexible dissolvable sheets addresses premature rupture and gelation issues, ensuring effective long-term freshness delivery by maintaining structural integrity.
Patent Information
- Application Number
- JP2022536544
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-19
- Filing Date
- 2021-04-16
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-04-16
AI Technical Summary
Existing flexible and dissolvable sheets containing perfume microcapsules (PMCs) face premature rupture and gelation issues due to the incorporation of PMCs in a slurry form, leading to incomplete dissolution and structural integrity problems, especially in multilayer structures under stringent cleaning conditions.
The method involves directly adding PMCs to a wet premix before aeration and drying steps, ensuring the microcapsules remain intact and are distributed between the sheet's surfaces, using a viscous premix and controlled aeration to protect the PMCs from damage and prevent gelation.
This approach enhances the dissolution profile and reduces gelation, allowing effective long-term delivery of freshness benefits by maintaining the integrity of PMCs throughout the processing steps.
Smart Images

Figure 0007605842000013 
Figure 0007605842000014 
Figure 0007605842000015
Abstract
Description
[Technical field]
[0001] The present disclosure relates to flexible, porous, dissolvable solid articles containing direct-loading microcapsules therein for delivering benefit agents and methods for making the same. [Background technology]
[0002] Flexible and dissolving sheets containing surfactants and / or other active ingredients in a water-soluble polymer carrier or matrix are well known. Such sheets are particularly useful for delivering surfactants and / or other active ingredients upon dissolution in water. Compared to traditional granules or liquid forms in the same product category, such sheets have better structural integrity, are more concentrated, and are easier to store, transport / ship, carry, and handle. Compared to solid tablet forms in the same product category, such sheets are more flexible, less brittle, and have better sensory appeal to consumers.
[0003] It is particularly desirable to use such flexible and dissolvable sheets to deliver long-term freshness benefits (e.g., fragrance that lasts for days) or other sensory or functional benefits to consumers. Long-term freshness can be achieved by various mechanisms, among which perfume microcapsules (PMC) are becoming increasingly popular. For example, WO 2018 / 141096 discloses a method for incorporating PMC into flexible and dissolvable sheets after such sheets are formed (instead of incorporating the fracturable microcapsules in the original starting material used to form such sheets). Similarly, WO 2011 / 014643, which discloses forming flexible and dissolvable sheets with an open-celled foam (OCF) structure therein to further improve their dissolution, teaches in its Examples 13 and 14 to add PMC by spraying a slurry containing such microcapsules onto an already formed porous sheet. It was believed that PMC, being friable in nature, may burst or break under the heat, pressure, and / or shear forces applied during the sheet-forming process, prematurely releasing the perfume encapsulated therein. Accordingly, WO 2018 / 1411096(A) and WO 2011 / 014643 disclose the addition of PMC after sheet formation (i.e., "post-added" PMC), which may help maintain the structural integrity of such microcapsules and minimize premature bursting / breakage of the microcapsules.
[0004] However, severe gelling problems have been observed in flexible and dissolvable sheets containing post-added PMC, especially when such sheets contain OCF structures therein. Without being bound by any theory, it is believed that because the PMC is provided in a slurry form (containing a significant amount of water), the excess water in the PMC-containing slurry accidentally dissolves the portion of the sheet that first comes into contact with the slurry, resulting in the collapse of the OCF structure and the formation of a slowly dissolving gel layer in that portion. The gelling problem may be further exacerbated when multiple layers of such flexible and dissolvable sheets are assembled together to form a multi-layer structure to deliver the required dose of surfactant / active for one wash cycle or one wash need. As a result, such a multi-layer structure may not completely dissolve, especially when exposed to certain stringent wash conditions (e.g., cold water or very hard water, or low water wash conditions). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2018 / 141096 [Patent Document 2] International Publication No. 2011 / 014643 [Patent Document 3] International Publication No. 2018 / 1411096(A) Summary of the Invention [Problem to be solved by the invention]
[0006] Accordingly, there is a need to improve the dissolution profile and reduce gelling of flexible and dissolvable sheets containing OCF structures therein along with PMC and / or other active-containing microcapsules, and also enable effective delivery of long-term freshness benefits and / or other sensory / functional benefits to the consumer. [Means for solving the problem]
[0007] The dissolution profile of the above-mentioned flexible and dissolvable sheet can be significantly improved and the gelation problem can be effectively reduced, while PM C and and / or other active-containing microcapsules (i.e., "direct-add" PMCs or other microcapsules) A slurry containing It is a surprising and unexpected discovery of the present disclosure that the aeration, sheet-forming, and drying steps of PMC and / or other active-containing microcapsules can be added directly to the wet premix to create a flexible and dissolvable sheet, effectively delivering long-term freshness benefits and / or other sensory / functional benefits to the consumer. Contrary to conventional wisdom, the present disclosure finds that the aeration, sheet-forming, and drying steps do not cause significant damage to the PMC and / or other active-containing microcapsules, and that the majority of such directly added PMC and / or other active-containing microcapsules survive such processing steps intact and are capable of delivering the desired long-term freshness benefits and / or other sensory / functional benefits. Without being bound by any theory, it is believed that the combination of the viscous wet premix and the air bubbles generated during the aeration step function to suspend and protect the PMC and / or other active-containing microcapsules against external pressures or forces. Furthermore, the subsequent drying step is 、P MC and / or other active substance-containing microcapsules A slurry containing The excess water introduced by is removed at a well-controlled temperature, thereby, on the one hand, preventing such water from dissolving / damaging the OCF structure and causing gelling problems in the resulting solid sheet article, and, on the other hand, avoiding overheating that may rupture / break the PMC.
[0008] In one aspect, the present disclosure relates to a method for preparing a solid sheet article, the method comprising: a) providing a wet premix comprising a water soluble polymer, a surfactant, and microcapsules, the wet premix having a viscosity measured at 40° C. and 1 s of from 1,000 cps to 25,000 cps, each of the microcapsules comprising a core and a shell at least partially surrounding the core, the core comprising a benefit agent; b) aerating the wet premix to form an aerated wet premix having a density of 0.05 to 0.5 g / mL; c) forming the aerated wet premix into a sheet; and d) drying the formed sheet at a temperature between 70° C. and 200° C. for a drying time between 1 minute and 60 minutes to form the solid sheet article.
[0009] In another aspect, the present disclosure relates to a flexible porous dissolvable solid sheet article comprising a water soluble polymer, a surfactant, and a plurality of microcapsules, the solid sheet article having opposing first and second planar surfaces, each of the plurality of microcapsules comprising a core and a shell at least partially surrounding the core, the core comprising a benefit agent, at least one of the microcapsules being located between the opposing first and second planar surfaces, the solid sheet article being characterized by (i) a percent open cell content of 80% to 100%, and (ii) an overall average pore size of 100 μm to 2000 μm. Preferably, a majority of the plurality of microcapsules are located between the opposing first and second planar surfaces of the solid sheet article.
[0010] In another aspect, the present disclosure relates to a multi-layer structure comprising two or more layers of the flexible porous dissolvable solid sheet article described above.
[0011] These and other aspects of the present invention will become more apparent from a reading of the following detailed description. [Brief description of the drawings]
[0012] [Figure 1A]FIG. 1 is a schematic diagram of an exemplary flexible porous dissolvable solid sheet article according to the present disclosure. [Figure 1B] FIG. 1B is a cross-sectional view of FIG. 1A taken along line AA in FIG. 1A. [Diagram 2] FIG. 1 is a schematic diagram of a microcapsule according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] I. Definition As used herein, the term "flexible" refers to the ability of an article to withstand stress when bent 90° along a centerline perpendicular to its length without breaking or significant disruption. Preferably, such articles are capable of undergoing significant elastic deformation and are characterized by a Young's modulus of 5 GPa or less, preferably 1 GPa or less, more preferably 0.5 GPa or less, and most preferably 0.2 GPa or less.
[0014] As used herein, the term "solubility" refers to the ability of an article to completely or substantially dissolve in a sufficient amount of deionized water at 20° C. and atmospheric pressure within 8 hours without any agitation, with less than 5% by weight remaining as an insoluble residue.
[0015] As used herein, the term "solid" refers to the ability of an article to substantially retain its shape (i.e., without any visible change in its shape) at 20° C. and atmospheric pressure when the article is unconstrained and no external forces are applied to the article.
[0016] As used herein, the term "sheet" refers to a non-fibrous structure having a three-dimensional shape, i.e., thickness, length, and width, while the aspect ratios of length to thickness and width to thickness are both at least about 5:1, and the length to width ratio is at least about 1:1. Preferably, the aspect ratios of length to thickness and width to thickness are both at least about 10:1, more preferably at least about 15:1, and most preferably at least about 20:1, and the aspect ratio of length to width is preferably at least about 1.2:1, more preferably at least about 1.5:1, and most preferably at least about 1.618:1.
[0017] As used herein, the term "water solubility" refers to the ability of a sample material to completely dissolve or disperse in water without leaving any visible solids or forming any visible separate phases, when at least about 25 grams, preferably at least about 50 grams, more preferably at least about 100 grams, and most preferably at least about 200 grams of such material are placed in 1 liter (1 L) of deionized water at 20° C. and atmospheric pressure with sufficient agitation.
[0018] As used herein, the terms "aerate", "aerating" or "aeration" refer to the process of introducing gas into a liquid or pasty composition by mechanical and / or chemical means.
[0019] As used herein, the term "open cell foam" or "open cell pore structure" refers to a solid interconnected polymer-containing matrix that contains a gas, typically a gas (such as air), and defines a network of voids or cells that do not collapse the foamed structure during the drying process, thereby maintaining physical strength and solid coherence. The interconnectedness of the structure may be described by the percent open cell content, as measured by Test 3 disclosed below.
[0020] The terms "essentially free of" or "essentially free from" mean that the indicated substance is present in such small amounts that it has not been intentionally added to a composition or product, or preferably is not present in such composition or product at concentrations detectable by analysis. Compositions or products may be included in which the indicated substance is present only as an impurity of one or more substances intentionally added to such composition or product.
[0021] As used herein, the term "bottom surface" refers to the surface of the flexible porous dissolvable solid sheet of the present disclosure that is in direct contact with the support surface on which the sheet of aerated wet premix is placed during the drying process, while the term "top surface" refers to the surface of the sheet opposite the bottom surface. Furthermore, such a solid sheet can be divided along its thickness into three regions, including a top region adjacent its top surface, a bottom region adjacent its bottom surface, and a middle region located between the top and bottom regions. The top, middle, and bottom regions are equal in thickness, i.e., each has a thickness of about 1 / 3 of the total thickness of the sheet.
[0022] As used herein, the term "heating direction" refers to a direction in which a heat source applies thermal energy to an article, resulting in a temperature gradient in such an article that decreases from one side of such an article to the other side. For example, if a heat source located on one side of an article applies thermal energy to the article to generate a temperature gradient that decreases from one side to the other side, the heating direction is then considered to extend from one side to the other side. If both sides of such an article or different portions of such an article are heated simultaneously without an observable temperature gradient across such an article, then the heating occurs in a non-directional manner and there is no heating direction.
[0023] As used herein, the terms "substantially opposite" or "substantially offset" refer to two directions or two lines that have an offset angle between them of 90° or more.
[0024] As used herein, the terms "substantially aligned" or "substantial alignment" refer to two directions or two lines that have an offset angle between them of less than 90°.
[0025] As used herein, the term "primary heat source" refers to a heat source that provides more than 50%, preferably more than 60%, more preferably more than 70%, and most preferably more than 80% of the total heat energy absorbed by an object (e.g., a sheet of aerated wet premix according to the present disclosure).
[0026] As used herein, the term "controlled surface temperature" refers to a surface temperature that is relatively stable, i.e., having less than + / - 20% variation, preferably less than + / - 10% variation, and more preferably less than + / - 5% variation.
[0027] II. Solid Sheet Formulation The flexible porous dissolvable solid sheet article of the present disclosure comprises at least a water-soluble polymer, a surfactant, and a plurality of microcapsules. It may optionally comprise other auxiliary ingredients. Compared to the prior art, the post-added PMC or other microcapsules remain only on one or both planar surfaces of the sheet article to which they are added, whereas the direct-added PMC or other microcapsules of the present disclosure are located inside the flexible porous dissolvable solid sheet article and between two opposing planar surfaces of such solid sheet article.
[0028] To better illustrate this, Figures 1A and 1B show a schematic and cross-sectional view of an exemplary flexible porous dissolvable solid sheet article 1 having opposed first and second planar surfaces 2, 4. At least one of the microcapsules 10 is located between the opposed first and second surfaces 2, 4 in a matrix 20 formed by a water-soluble polymer, a surfactant, and optionally other auxiliary ingredients (not shown). Preferably, the majority of the microcapsules 10, more preferably greater than 80%, even more preferably greater than 90%, and most preferably greater than 90%, are located between the opposed first and second surfaces 2, 4.
[0029] 1. Microcapsules Each of the plurality of microcapsules may include a core and a shell at least partially surrounding the core. As shown generally in FIG. 2, the microcapsule 10 may have a core 30 and a shell 20 at least partially surrounding the core 30. The core 30 may include a benefit agent, such as a fragrance. The shell 20 may have an outer surface 25, which may have a coating 40. The coating may be cationic, nonionic, or anionic. These elements are described in more detail below.
[0030] Preferably, the flexible porous dissolvable solid sheet article of the present disclosure comprises the plurality of microcapsules in an amount ranging from about 0.1%, or about 0.2%, or about 0.5%, or about 1%, or about 50%, or about 40%, or about 30%, or about 20%, based on the total weight of the flexible porous dissolvable solid sheet article. Preferably, the solid article comprises from about 0.1% to about 50%, more preferably from about 0.2% to about 40%, even more preferably from about 0.5% to about 30%, and most preferably from about 1% to about 20% of the microcapsules based on the total weight of the flexible porous dissolvable solid sheet article.
[0031] The core of each of the microcapsules may contain any of the following: fragrances, silicone oils, waxes, hydrocarbons, higher fatty acids, essential oils, lipids, skin cooling agents, vitamins, sunscreens, antioxidants, glycerin, catalysts, bleach particles, silicone dioxide particles, odor reducing agents, odor control materials, chelating agents, antistatic agents, fabric softeners, insect and moth repellents, colorants, thickeners, drape and foam conditioning agents, smoothing agents, wrinkle control agents, sanitizing agents, disinfectants, bacterial inhibitors, mold inhibitors, mildew inhibitors, antiviral agents, drying agents, stain resistant agents, soil release agents, and the like. The benefit agent may be selected from the group consisting of: bleaching agents, fabric refreshing agents, fresh wash maintenance agents, chlorine bleach odor control agents, dye fixatives, dye transfer inhibitors, color retention agents, optical brighteners, color restoration / renewal agents, anti-fade agents, whiteness enhancers, anti-abrasion agents, abrasion resistance agents, fabric integration agents, anti-wear agents, foam suppressants, defoamers, UV protection agents, sun fade inhibitors, anti-allergy agents, enzymes, waterproofing agents, fabric comfort agents, shrink resistance agents, stretch resistance agents, stretch recovery agents, skin care agents, natural actives, antimicrobial actives, antiperspirant actives, cationic polymers, dyes, and mixtures thereof. Preferably, the benefit agent comprises a fragrance.
[0032] The shell, which at least partially (preferably completely) surrounds the core, may comprise a material selected from the group consisting of polyethylene, polyamide, polyacrylamide, polystyrene, polyisoprene, polycarbonate, polyester, polyacrylate, polymethacrylate, aminoplast, polyvinylamine, polyvinylformamide, polyolefin, polyvinyl alcohol, polysaccharides (e.g., alginate and / or chitosan), gelatin, shellac, epoxy resin, vinyl polymer, water-insoluble inorganics (e.g., silica), silicone, and combinations thereof. Among these materials, the most stable are polyoxymethyleneurea (PMU)-based materials, including but not limited to urea-formaldehyde and / or melamine-formaldehyde.
[0033] In one embodiment, the shell comprises an aminoplast polymer selected from the group consisting of polyurea, polyurethane, and / or polyurea urethane. UreaPreferably, the shell comprises an aminoplast copolymer, such as melamine-formaldehyde, crosslinked melamine-formaldehyde, urea-formaldehyde, crosslinked urea-formaldehyde, and combinations thereof. More preferably, each shell of the microcapsule comprises melamine-formaldehyde and / or crosslinked melamine-formaldehyde.
[0034] In a preferred but not required aspect of the present disclosure, the shell comprises an anionic polymer selected from the group consisting of poly(meth)acrylate, polyvinyl(meth)acrylate, poly(ethylene-maleic anhydride), and combinations thereof. More preferably, the shell of each of the microcapsules comprises a polyacrylate.
[0035] Optionally, each shell of the microcapsules may have one or more coatings formed thereon. The coatings may be cationic, nonionic, and / or anionic, and may include, but are not limited to, poly(meth)acrylates, poly(ethylene-maleic anhydride), polyamines, waxes, polyvinylpyrrolidone, polyvinylpyrrolidone copolymers, polyvinylpyrrolidone-ethyl acrylate, polyvinylpyrrolidone-vinyl acrylate, polyvinylpyrrolidone-methyl acrylate, polyvinyl acetals, polyvinyl butyrals, polysiloxanes, poly(propylene maleic anhydride), maleic anhydride derivatives, copolymers of maleic anhydride derivatives, polyvinyl alcohol, styrene-butadiene latex, gelatin, etc. The composition may include materials selected from the group consisting of gum arabic, carboxymethyl cellulose, carboxymethyl hydroxyethyl cellulose, hydroxyethyl cellulose, other modified celluloses, sodium alginate, chitosan, casein, pectin, modified starch, polyvinyl methyl ether / maleic anhydride, poly(vinylpyrrolidone / methacrylamidopropyl trimethyl ammonium chloride), polyvinylpyrrolidone / dimethylaminoethyl methacrylate, polyvinylamine, polyallylamine, and copolymers of polyvinylamine, polyvinyl formamide, and mixtures thereof.Preferably, the coating comprises a material selected from the group consisting of poly(meth)acrylates, poly(ethylene-maleic anhydride), polyamines, polyvinylpyrrolidone, polyvinylpyrrolidone-ethyl acrylate, polyvinylpyrrolidone-vinyl acrylate, polyvinylpyrrolidone methyl acrylate, polyvinylpyrrolidone / vinyl acetate, polyvinyl acetal, polyvinyl butyral, polysiloxanes, poly(propylene maleic anhydride), maleic anhydride derivatives, copolymers of maleic anhydride derivatives, polyvinyl alcohol, carboxymethyl cellulose, carboxymethyl hydroxyethyl cellulose, hydroxyethyl cellulose, polyvinyl methyl ether / maleic anhydride, poly(vinylpyrrolidone / methacrylamidopropyl trimethyl ammonium chloride), polyvinylpyrrolidone / dimethylaminoethyl methacrylate, polyvinylamine, polyvinylformamide, polyallylamine, and copolymers of polyvinylamine, copolymers of polyvinylformamide, copolymers of polyallylamine, and mixtures thereof. Most preferably, the coating comprises a material selected from the group consisting of poly(meth)acrylates, poly(ethylene-maleic anhydride), polyamines, polyvinylpyrrolidone, polyvinylpyrrolidone-ethyl acrylate, polyvinylpyrrolidone-vinyl acrylate, polyvinylpyrrolidone methyl acrylate, polyvinylpyrrolidone / vinyl acetate, polyvinyl acetal, polysiloxanes, poly(propylene maleic anhydride), maleic anhydride derivatives, copolymers of maleic anhydride derivatives, polyvinyl alcohol, carboxymethyl cellulose, carboxymethyl hydroxyethyl cellulose, hydroxyethyl cellulose, polyvinyl methyl ether / maleic anhydride, polyvinylpyrrolidone / dimethylaminoethyl methacrylate, polyvinylamine, polyvinylformamide, polyallylamine, and copolymers of polyvinylamine, copolymers of polyvinylformamide, copolymers of polyallylamine, and mixtures thereof.
[0036] In a preferred embodiment of the present disclosure, each shell of the microcapsules has a cationic coating thereon, while the cationic coating is formed by a cationic polymer selected from the group consisting of polyvinylformamide, partially hydroxylated polyvinylformamide, polyvinylamine, polyethyleneimine, ethoxylated polyethyleneimine, cationically modified polysaccharides (e.g., cationically modified starch, cationically modified guar, cationically modified hydroxyl ethyl cellulose, etc.), and combinations thereof.
[0037] In another example, the coating that coats the shell of each of the microcapsules described above comprises a cationic polymer and an anionic polymer.
[0038] The microcapsules used in the present disclosure are preferably friable microcapsules, i.e., have a tendency to burst or break open when subjected to external pressure or shear forces. Fracturable microcapsules as referred to herein are activated by external pressure or force to release the benefit agent encapsulated in the core, and are thus distinguished from moisture-activated microcapsules, such as those mostly formed by cyclodextrins.
[0039] The microcapsules of the present disclosure can be formed by a variety of procedures including, but not limited to, coating, extrusion, spray drying, interfacial polymerization, in situ polymerization, and matrix polymerization.
[0040] The microcapsules may have a volume weighted average particle size ranging from about 5 micrometers to about 500 micrometers, preferably from about 8 micrometers to about 200 micrometers, and more preferably from about 10 micrometers to about 100 micrometers, as measured by typical methods known in the art, such as a Malvern Particle Sizer (commercially available from Malvern Panalytical, Ltd., Malvern, UK).
[0041] 2. Water-soluble polymers As mentioned above, the flexible porous dissolvable solid sheets of the present disclosure may be formed by a wet premix comprising a water-soluble polymer, a surfactant, and a plurality of microcapsules. Such water-soluble polymer may function as a film former, a structurant, and a carrier for other active ingredients (e.g., surfactants, emulsifiers, builders, chelating agents, fragrances, colorants, etc.) in the resulting solid sheet.
[0042] Preferably, the wet premix may comprise from about 3% to about 20% water soluble polymer by weight of the premix, in one embodiment from about 5% to about 15% water soluble polymer by weight of the premix, and in one embodiment from about 7% to about 10% water soluble polymer by weight of the premix.
[0043] After drying, the water-soluble polymer is preferably present in the flexible porous dissolvable solid sheet of the present disclosure in an amount ranging from about 5% to about 50%, preferably from about 8% to about 40%, more preferably from about 10% to about 30%, and most preferably from about 11% to about 25%, based on the total weight of the solid sheet. In particularly preferred embodiments of the present disclosure, the total amount of water-soluble polymer present in the flexible porous dissolvable solid sheet of the present disclosure is 25% or less, based on the total weight of such sheet.
[0044] Suitable water-soluble polymers for the practice of the present disclosure may be selected having a weight average molecular weight ranging from about 50,000 to about 400,000 Daltons, preferably from about 60,000 to about 300,000 Daltons, more preferably from about 70,000 to about 200,000 Daltons, and most preferably from about 80,000 to about 150,000 Daltons. The weight average molecular weight is calculated by adding the average molecular weight of each polymer raw material multiplied by its relative weight percentage by weight of the total weight of the polymer present in the porous solid sheet. The weight average molecular weight of the water-soluble polymer used herein may affect the viscosity of the wet premix, which in turn may affect the number and size of bubbles during the aeration step, and the pore expansion / opening results during the drying step. Additionally, the weight average molecular weight of the water-soluble polymer may affect the overall film-forming properties of the wet premix, and its compatibility / incompatibility with certain surfactants.
[0045] Water soluble polymers of the present disclosure may include, but are not limited to, synthetic polymers including polyvinyl alcohol, polyvinylpyrrolidone, polyalkylene oxides, polyacrylates, caprolactams, polymethacrylates, polymethyl methacrylates, polyacrylamides, polymethylacrylamides, polydimethylacrylamides, polyethylene glycol monomethacrylates, copolymers of acrylic acid and methyl acrylate, polyurethanes, polycarboxylic acids, polyvinyl acetates, polyesters, polyamides, polyamines, polyethyleneimines, maleic acid / (acrylate or methacrylate) copolymers, copolymers of methyl vinyl ether and maleic anhydride, copolymers of vinyl acetate and crotonic acid, copolymers of vinylpyrrolidone and vinyl acetate, copolymers of vinylpyrrolidone and caprolactam, copolymers of vinylpyrrolidone / vinyl acetate, copolymers of anionic, cationic and amphoteric monomers, and combinations thereof.
[0046] The water soluble polymers of the present disclosure may also be selected from polymers of natural origin, including those of vegetable origin, with examples such as karaya gum, tragacanth gum, gum arabic, acemannan, konjac mannan, acacia gum, ghatti gum, whey protein isolate, and soy protein isolate; seed extracts, including guar gum, locust bean gum, quince seed, and psyllium seed; seaweed extracts, such as carrageenan, alginic acid, and agar; fruit extracts (pectins); those of microbial origin, including xanthan gum, gellan gum, pullulan, hyaluronic acid, chondroitin sulfate, and dextran; and those of animal origin, including casein, gelatin, keratin, keratin hydrolysate, keratin sulfonate, albumin, collagen, glutelin, glucagon, gluten, zein, and shellac.
[0047] Modified natural polymers can also be used as water-soluble polymers in the present disclosure.Suitable modified natural polymers include, but are not limited to, cellulose derivatives such as hydroxypropylmethylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, methylcellulose, hydroxypropylcellulose, ethylcellulose, carboxymethylcellulose, cellulose acetate phthalate, nitrocellulose and other cellulose ethers / esters, and guar derivatives such as hydroxypropylcellulose.
[0048] The water-soluble polymer of the present disclosure may comprise starch. As used herein, the term "starch" includes both naturally occurring starch and modified starch. Typical natural sources of starch can include cereals, tubers, roots, legumes and fruits. More specific natural sources can include corn, beans, potatoes, bananas, barley, wheat, rice, sago, amaranth, tapioca, arrowroot, canna, sweet sorghum, and their waxy or higher amylase species. Native starch can be modified by any modification method known in the art to form modified starches, including physically modified starches such as sheared or thermally inhibited starches, crosslinked, acetylated, and organic esterified, hydroxyethylated, and hydroxypropylated, phosphorylation, and inorganic esterified, chemically modified starches such as cationic, anionic, nonionic, amphoteric and zwitterionic, and their succinate and substituted succinate derivatives, conversion products derived from starch including oxidation, enzymatic conversion, acid hydrolysis, heat or acid dextrinization, fluid or thin cooked starches prepared by heat and / or sheared products, heat and / or sheared products that may be useful herein, and pregelatinized starches known in the art.
[0049] Preferred water-soluble polymers of the present disclosure include polyvinyl alcohol, polyvinylpyrrolide, polyalkylene oxide, starch and starch derivatives, pullulan, gelatin, hydroxypropylmethylcellulose, methylcellulose, and carboxymethylcellulose. More preferred water-soluble polymers of the present disclosure include polyvinyl alcohol and hydroxypropylmethylcellulose.
[0050] The most preferred water-soluble polymer of the present disclosure is polyvinyl alcohol characterized by a degree of hydrolysis ranging from about 40% to about 100%, preferably from about 50% to about 95%, more preferably from about 65% to about 92%, and most preferably from about 70% to about 90%. Commercially available polyvinyl alcohols include those available under the tradename CELVOL from Celanese Corporation (Texas, USA), including but not limited to those available under the tradenames CELVOL 523, CELVOL 530, CELVOL 540, CELVOL 518, CELVOL 513, CELVOL 508, CELVOL 504, those available under the tradenames Mowiol® and POVAL® from Kuraray Europe GmbH (Frankfurt, Germany), PVA 1788 (also referred to as PVA BP17) available from various sources including Lubon Vinylon Co. (Nanjing, China), and combinations thereof. In a particularly preferred embodiment of the present disclosure, the flexible porous dissolvable solid sheet comprises from about 10% to about 25%, more preferably from about 15% to about 23%, of polyvinyl alcohol having a weight average molecular weight in the range of 80,000 to about 150,000 Daltons and a degree of hydrolysis in the range of about 80% to about 90%, based on the total weight of such sheet.
[0051] In addition to polyvinyl alcohol as described above, a single starch or a combination of starches may be used as a filler material in an amount that reduces the overall concentration of water-soluble polymer required, as long as it helps provide a solid sheet with the requisite structure and physical / chemical properties as described herein. However, too much starch may affect the solubility and structural integrity of the sheet. Therefore, in a preferred embodiment of the present disclosure, the solid sheet preferably contains 20% or less starch, preferably 0%-10%, more preferably 0%-5%, and most preferably 0%-1% by weight of the solid sheet.
[0052] 3. Surfactants In addition to the water-soluble polymers described above, the solid sheets of the present disclosure include at least one surfactant, which may act as an emulsifier during the aeration process to generate a sufficient amount of stable bubbles to form the desired OCF structure of the present disclosure, and may act as an active ingredient to achieve the desired cleaning effect.
[0053] In a preferred embodiment of the present disclosure, the solid sheet comprises a surfactant selected from the group consisting of anionic surfactants, nonionic surfactants, cationic surfactants, zwitterionic surfactants, amphoteric surfactants, polymeric surfactants, and any combination thereof.Different surfactants can be selected depending on the desired application of such solid sheet and the desired consumer benefits to be achieved.One advantage of the present disclosure is that the OCF structure of the solid sheet allows it to incorporate high surfactant content while still providing fast dissolution.As a result, high concentration cleaning composition can be formulated into the solid sheet of the present disclosure to provide consumers with a new and excellent cleaning experience.
[0054] Surfactants as used herein may include surfactants both in the conventional sense (i.e., surfactants that provide a consumer-perceived lathering effect) and emulsifiers (i.e., those that do not provide any lathering performance, but are intended primarily as processing aids in creating a stable foam structure). Examples of emulsifiers used as surfactant components herein include mono- and di-glycerides, fatty alcohols, polyglycerol esters, propylene glycol esters, sorbitan esters, and other emulsifiers commonly used to stabilize the air interface by known or otherwise methods.
[0055] The total amount of surfactant present in the solid sheet of the present disclosure may range from about 5% to about 90%, preferably about 10% to about 80%, more preferably about 30% to about 70%, based on the total weight of the solid sheet. As a result, the wet premix may contain from about 1% to about 40% surfactant based on the weight of the wet premix, in one embodiment from about 2% to about 35% surfactant based on the weight of the wet premix, and in one embodiment from about 5% to about 30% surfactant based on the weight of the wet premix.
[0056] In a preferred embodiment of the present disclosure, the solid sheet of the present disclosure comprises about 30% to about 90%, preferably about 40% to about 80%, more preferably about 50% to about 70% of one or more surfactants based on the total weight of the solid sheet. In such a case, the wet premix may comprise about 10% to about 40% of a surfactant based on the weight of the wet premix, in one embodiment about 12% to about 35% of a surfactant based on the weight of the wet premix, and in one embodiment about 15% to about 30% of a surfactant based on the weight of the wet premix.
[0057] Non-limiting examples of anionic surfactants suitable for use herein include alkyl and alkyl ether sulfates, sulfated monoglycerides, sulfonated olefins, alkylaryl sulfonates, primary or secondary alkane sulfonates, alkyl sulfosuccinates, acyltaurates, acyl isethionates, alkyl glyceryl ether sulfonates, sulfonated methyl esters, sulfonated fatty acids, alkyl phosphates, acyl glutamates, acyl sarcosinates, alkyl sulfoacetates, acylated peptides, alkyl ether carboxylates, acyl lactylates, anionic fluorosurfactants, sodium lauroyl glutamate, and combinations thereof.
[0058] One category of anionic surfactants that are particularly suitable for the practice of the present disclosure is C6-C 20Examples of suitable surfactants that can be used in the present disclosure include linear alkylbenzene sulphonate (LAS) surfactants. LAS surfactants are well known in the art and can be readily obtained by sulfonating commercially available linear alkylbenzenes. 10 ~C 20 As linear alkylbenzene sulfonates, C 10 ~C 20 Alkali metal salts, alkaline earth metal salts, or ammonium salts of linear alkylbenzene sulfonic acid, preferably C 11 ~C 18 Or C 11 ~C 14 Examples of the salts include sodium, potassium, magnesium, and / or ammonium salts of linear alkylbenzene sulfonic acid. More preferred are 12 and / or C. 14 The sodium or potassium salt of linear alkylbenzene sulfonic acid is preferably C 12 and / or C. 14 The sodium salts of linear alkylbenzene sulfonates, i.e., sodium dodecylbenzene sulfonate or sodium tetradecylbenzene sulfonate.
[0059] LAS provides excellent cleaning effects and is particularly suitable for use in laundry detergent applications. It was a surprising and unexpected discovery of the present disclosure that when polyvinyl alcohol having a higher weight average molecular weight (e.g., about 50,000 to about 400,000 Daltons, preferably about 60,000 to about 300,000 Daltons, more preferably about 70,000 to about 200,000 Daltons, most preferably about 80,000 to about 150,000 Daltons) is used as the film former and carrier, LAS can be used as the primary surfactant, i.e., can be present in an amount of more than 50% by weight of the total surfactant content in the solid sheet without adversely affecting the film forming performance and stability of the overall composition. Correspondingly, in certain embodiments of the present disclosure, LAS is used as the primary surfactant in the solid sheet. When LAS is present in the solid sheet of the present disclosure, the amount thereof may range from about 10% to about 70%, preferably from about 20% to about 65%, and more preferably from about 40% to about 60%, based on the total weight of the solid sheet.
[0060] Another category of anionic surfactants suitable for the practice of the present disclosure includes sodium trideceth sulfates (STS) having a weight average degree of alkoxylation ranging from about 0.5 to about 5, preferably from about 0.8 to about 4, more preferably from about 1 to about 3, and most preferably from about 1.5 to about 2.5. Trideceth, in one embodiment, is a 13 carbon branched alkoxylated hydrocarbon containing an average of at least one methyl branch per molecule. STS used in the present disclosure can include ST(EOxPOy)S, where EOx represents a repeating ethylene oxide unit with a repeat number x ranging from 0 to 5, preferably from 1 to 4, more preferably from 1 to 3, and POy represents a repeating propylene oxide unit with a repeat number y ranging from 0 to 5, preferably from 0 to 4, more preferably from 0 to 2. For example, it is understood that a material such as ST2S having a weight average degree of ethoxylation of about 2 may contain significant amounts of molecules with no ethoxylates, 1 mole of ethoxylate, 3 moles of ethoxylate, etc., and the distribution of ethoxylation can be broad, narrow, or truncated and still result in a total weight average degree of ethoxylation of about 2. It was a surprising and unexpected discovery of the present disclosure that STS is particularly suitable for personal cleansing applications, and that when polyvinyl alcohol having a higher weight average molecular weight (e.g., about 50,000 to about 400,000 daltons, preferably about 60,000 to about 300,000 daltons, more preferably about 70,000 to about 200,000 daltons, most preferably about 80,000 to about 150,000 daltons) is used as the film former and carrier, STS can be used as the primary surfactant, i.e., can be present in an amount of more than 50% based on the weight of the total surfactant content in the solid sheet without adversely affecting the film forming performance and stability of the overall composition. Correspondingly, in certain embodiments of the present disclosure, STS is used as the primary surfactant in the solid sheet. When STS is present in the solid sheet of the present disclosure, the amount can range from about 10% to about 70%, preferably about 20% to about 65%, more preferably about 40% to about 60%, based on the total weight of the solid sheet.
[0061] Another category of anionic surfactants suitable for the practice of the present disclosure includes the alkyl sulfates. These materials have the corresponding formula: ROSO3M, where R is an alkyl or alkenyl of about 6 to about 20 carbon atoms, x is 1 to 10, and M is a water soluble cation such as ammonium, sodium, potassium, and triethanolamine. Preferably, R has about 6 to about 18, preferably about 8 to about 16, and more preferably about 10 to about 14 carbon atoms. As previously mentioned, the non-alkoxylated C6-C 20 Linear or branched alkyl sulfates (AS) are considered preferred surfactants in soluble solid sheets, especially as the primary surfactant therein, due to their compatibility with low molecular weight polyvinyl alcohols (e.g., those having a weight average molecular weight of 50,000 Daltons or less) in film-forming performance and stability. However, it was a surprising and unexpected discovery of the present disclosure that when polyvinyl alcohols having higher weight average molecular weights (e.g., about 50,000 to about 400,000 Daltons, preferably about 60,000 to about 300,000 Daltons, more preferably about 70,000 to about 200,000 Daltons, most preferably about 80,000 to about 150,000 Daltons) are used as film formers and carriers, other surfactants (e.g., LAS and / or STS) can be used as the primary surfactant in the solid sheet without adversely affecting the film-forming performance and stability of the overall composition. Therefore, in particularly preferred embodiments of the present disclosure, it is desirable to provide a solid sheet having no more than about 20% AS, preferably 0% to about 10%, more preferably 0% to about 5%, and most preferably 0% to about 1% AS, based on the weight of the solid sheet.
[0062] Another category of anionic surfactants suitable for practicing the present disclosure includes C6-C 20 Linear or branched chain alkylalkoxy sulfates (AAS) are also included. Within this category, the corresponding formula RO(C2H4O) xParticularly preferred are linear or branched alkylethoxy sulfates (AES) having the formula SO3M, where R is an alkyl or alkenyl of about 6 to about 20 carbon atoms, x is 1 to 10, and M is a water soluble cation such as ammonium, sodium, potassium, and triethanolamine. Preferably, R has about 6 to about 18, preferably about 8 to about 16, more preferably about 10 to about 14 carbon atoms. AES surfactants are typically made as the condensation product of ethylene oxide with a monohydric alcohol having about 6 to about 20 carbon atoms. Useful alcohols can be derived from fats, such as coconut oil or tallow, or can be synthetic. Preferred herein are lauryl alcohol and linear alcohols derived from coconut oil. Such alcohols are reacted with a molar proportion of ethylene oxide of about 1 to about 10, preferably about 3 to about 5, especially about 3, and the resulting mixture of molecular species having, for example, an average of 3 moles of ethylene oxide per mole of alcohol is sulfated and neutralized. Highly preferred AESs include mixtures of individual compounds, the mixtures having an average alkyl chain length of about 10 to about 16 carbon atoms and an average degree of ethoxylation of about 1 to about 4 moles of ethylene oxide. When an AAS is present in the solid sheet of the present disclosure, the amount may range from about 2% to about 40%, preferably from about 5% to about 30%, more preferably from about 8% to about 12%, based on the total weight of the solid sheet.
[0063] Other suitable anionic surfactants include those having the general formula [R 1 -SO-M], wherein R 1 is selected from the group consisting of linear or branched saturated aliphatic hydrocarbon radicals having from about 6 to about 20, preferably from about 10 to about 18 carbon atoms, and M is a cation. 10~18n-Paraffins are preferred. Other suitable anionic surfactants include olefin sulfonates having from about 12 to about 24 carbon atoms. The α-olefins from which the olefin sulfonates are derived are mono-olefins having from about 12 to about 24 carbon atoms, preferably from about 14 to about 16 carbon atoms. Preferably, they are straight chain olefins.
[0064] Another class of anionic surfactants suitable for use in fabric and home care compositions are the β-alkyloxyalkanesulfonates. These compounds have the formula:
[0065] [ka] In the formula, R1 is a straight chain alkyl group having from about 6 to about 20 carbon atoms, R2 is a lower alkyl group having from about 1 (preferably) to about 3 carbon atoms, and M is a water-soluble cation as described above.
[0066] Further examples of suitable anionic surfactants are reaction products of fatty acids esterified with isethionic acid and neutralized with sodium hydroxide (e.g., the fatty acid is derived from coconut oil), such as the sodium or potassium salt of the fatty acid amide of methyl tauride, the fatty acid being derived from coconut oil. Still other suitable anionic surfactants are succinates, examples of which include disodium N-octadecyl sulfosuccinate, diammonium lauryl sulfosuccinate, tetrasodium N-(1,2-dicarboxyethyl)-N-octadecyl sulfosuccinamate, diamyl ester of sodium sulfosuccinate, dihexyl ester of sodium sulfosuccinate, and dioctyl ester of sodium sulfosuccinate.
[0067] Nonionic surfactants that may be included in the solid sheets of the present disclosure may be any conventional nonionic surfactant, including, but not limited to, alkyl alkoxylated alcohols, alkyl alkoxylated phenols, alkyl polysaccharides (especially alkyl glucosides and alkyl polyglucosides), polyhydroxy fatty acid amides, alkoxylated fatty acid esters, sucrose esters, sorbitan esters and alkoxylated derivatives of sorbitan esters, amine oxides, etc. Preferred nonionic surfactants are represented by the formula R 1 (OC2H4) n OH, wherein R 1 is C8~C 18 is an alkyl or alkylphenyl group, and n is from about 1 to about 80. Particularly preferred are C8-C12 nonionic surfactants having a weight average degree of ethoxylation of from about 1 to about 20, preferably from about 5 to about 15, and more preferably from about 7 to about 10, such as NEODOL® nonionic surfactants available from Shell. 18 Other non-limiting examples of nonionic surfactants useful herein include C6-C alkoxylated alcohols, where the alkoxylate units can be ethyleneoxy units, propyleneoxy units, or mixtures thereof. 12 Alkylphenol alkoxylate; C 12 ~C 18 C6-C with alcohol and ethylene oxide / propylene oxide block polymer 12 Alkylphenol condensates (such as Pluronic® (BASF)); C 14 ~C 22 Medium-chain branched alcohol (BA); C 14 ~C 22 Medium Branched Chain Alkyl Alkoxylate, BAE x (wherein x is 1 to 30); alkyl polysaccharides, particularly alkyl polyglycosides; polyhydroxy fatty acid amides; and ether-terminated poly(oxyalkylated) alcohol surfactants. Suitable nonionic surfactants also include those sold by BASF under the trade name Lutensol®.
[0068] In a preferred embodiment, the non-ionic surfactants selected from sorbitan esters and alkoxylated derivatives of sorbitan esters include sorbitan monolaurate (SPAN® 20), sorbitan monopalmitate (SPAN® 40), sorbitan monostearate (SPAN® 60), sorbitan tristearate (SPAN® 65), sorbitan monooleate (SPAN® 80), sorbitan trioleate (SPAN® 85), sorbitan isostearate, polyoxyethylene (20) sorbitan monolaurate (Tween® 20), Polyoxyethylene (20) sorbitan monopalmitate (Tween® 40), polyoxyethylene (20) sorbitan monostearate (Tween® 60), polyoxyethylene (20) sorbitan monooleate (Tween® 80), polyoxyethylene (4) sorbitan monolaurate (Tween® 21), polyoxyethylene (4) sorbitan monostearate (Tween® 61), polyoxyethylene (5) sorbitan monooleate (Tween® 81), all available from Uniqema, and combinations thereof.
[0069] The most preferred nonionic surfactants for the practice of the present disclosure are C6-C alkoxylated surfactants having a weight average degree of alkoxylation in the range of 5 to 15. 20 Linear or branched alkylalkoxylated alcohols (AA), more preferably C 10 having a weight average degree of alkoxylation in the range of 7 to 9 12 ~C 14 Linear ethoxylated alcohols can be mentioned. When AA type nonionic surfactants are present in the solid sheet of the present disclosure, the amount can be in the range of about 2% to about 40%, preferably about 5% to about 30%, more preferably about 8% to about 12%, based on the total weight of the solid sheet.
[0070] In a particularly preferred embodiment of the present disclosure, the majority of the surfactant in the flexible porous dissolvable solid sheet article is a C6-C 20 Linear alkylbenzene sulfonates (LAS), C6-C with weight average degree of alkoxylation ranging from 0.5 to 10 20 Linear or branched chain alkyl alkoxy sulfates (AAS), C6-C 20 Linear or branched alkyl sulfates (AS), C6-C with a weight average degree of alkoxylation ranging from 5 to 15 20 In the case of anionic and / or non-ionic surfactants selected from the group consisting of linear or branched alkyl alkoxylated alcohols (AA), and combinations thereof, the shell of each of the above-mentioned microcapsules preferably comprises an anionic polymer selected from the group consisting of poly(meth)acrylates, polyvinyl(meth)acrylates, poly(ethylene-maleic anhydride), and combinations thereof. Without being bound by any theory, it is believed that matching the surface charge of the microcapsules with the type of surfactant used in the solid sheet article may further help to reduce the risk of premature rupture / fracture of the microcapsules and preserve the structural integrity of such microcapsules.
[0071] Cationic surfactants may also be utilized in the present disclosure, particularly in fabric softener and hair conditioner products. When used in making products containing cationic surfactants as the primary surfactant, such cationic surfactants are preferably present in an amount ranging from about 2% to about 30%, preferably from about 3% to about 20%, more preferably from about 5% to about 15%, based on the total weight of the solid sheet.
[0072] For example, the cationic surfactant can be a quaternary ammonium compound and / or an amine compound.Representative quaternary ammonium compounds include, but are not limited to, alkylated quaternary ammonium compounds, cyclic or cyclic quaternary ammonium compounds, aromatic quaternary ammonium compounds, diquaternary ammonium compounds, alkoxylated quaternary ammonium compounds, amidoamine quaternary ammonium compounds, ester quaternary ammonium compounds, and mixtures thereof.
[0073] Preferred cationic surfactants of the present disclosure include diester quaternary ammonium (DEQA) compounds, C 12 ~C 22 Mono / di-alkyl quaternary ammonium compounds, C 12 ~C 22The cationic surfactant may include, but is not limited to, alkyl trimethyl ammonium compounds or their amine precursors, dialkyl dimethyl ammonium compounds or their amine precursors, methyl-diethanolamine-based (MDEA-based) quaternary ammonium compounds or their amine precursors, methyl-diisopropanolamine-based (MDIPA-based) quaternary ammonium compounds or their amine precursors, triethanolamine-based (TEA-based) quaternary ammonium compounds or their amine precursors, and any combination thereof. Most specifically, the cationic surfactant may be selected from the group consisting of behenyl trimethyl ammonium chloride; stearyl trimethyl ammonium chloride; cetyl trimethyl ammonium chloride; lauryl trimethyl ammonium chloride; hydrogenated tallow alkyl trimethyl ammonium chloride, dimethyl hydroxyethyl lauryl ammonium chloride, dialkyl (14-18) dimethyl ammonium chloride, ditallow alkyl dimethyl ammonium chloride, dihydrogenated tallow alkyl dimethyl ammonium chloride, distearyl dimethyl ammonium chloride, dicetyl dimethyl ammonium chloride, N,N-di(acyl-oxyethyl)-N,N-dimethyl ammonium chloride, N,N-di(acyl-oxyisopropyl)-N,N-dimethyl ammonium methyl sulfate, N,N-di(acyl-oxyethyl)-N,N-methyl hydroxyethyl ammonium methyl sulfate, and any combination thereof. Exemplary cationic surfactants include diethyl ester dimethyl ammonium chloride (DEEDMAC), dipropyl hydroxyethyl ammonium methosulfate, coconut trimethyl ammonium chloride, and lauryl trimethyl ammonium chloride.
[0074] In a particularly preferred embodiment of the present disclosure, the flexible porous dissolvable solid sheet article comprises a DEQA compound as the majority surfactant (i.e., present in an amount of more than 50% based on the weight of the total surfactant content in the solid sheet article). DEQA compounds include diamide actives and actives with a mixture of amide and ester bonds. Preferred DEQA compounds are typically made by reacting alkanolamines such as MDEA (methyldiethanolamine) and TEA (triethanolamine) with fatty acids. Some materials typically obtained from such reactions include N,N-di(acyl-oxyethyl)-N,N-dimethylammonium chloride or N,N-di(acyl-oxyethyl)-N,N-methylhydroxyethylammonium methylsulfate, where the acyl groups are derived from animal fats, unsaturated and polyunsaturated fatty acids.
[0075] Preferably, the cationic surfactant may include a DEQA compound of the formula: {R (4-m) -N + -[ZYR 1 ] m}X - where each R is hydrogen, a short chain C1-C6, in one embodiment a C1-C3 alkyl or hydroxyalkyl group (e.g., methyl, ethyl, propyl, hydroxyethyl, etc.), poly(C 2-3- each Z is independently (CH2)n, CH2-CH(CH3)-, or CH-(CH3)-CH2-; each Y can include -O-(O)C-, -C(O)-O-, -NR-C(O)-, or -C(O)-NR-; each m is 2; each R 1 The sum of the carbons in (plus 1 when Y is -O-(O)C- or -NR-C(O)-) is C 12 ~C 22 Or C 14 ~C 20 Each R 1 may be a hydrocarbyl or substituted hydrocarbyl group; X -may include any compatible anion. In one aspect, the compatible anions may include chloride, bromide, methyl sulfate, ethyl sulfate, sulfate, and nitrate. In another aspect, the compatible anions may include chloride or methyl sulfate. As used herein, when a diester is specified, it may include monoesters present.
[0076] A second type of DEQA compound ("DEQA(2)") suitable as an active for use as a cationic surfactant has the general formula: [R3N + CH2CH(YR 1 )(CH2YR 1 )]X - In the formula, each Y, R, R 1 , and X - has the same meaning as above. An example of a preferred DEQA(2) is the "propyl" ester quaternary ammonium fabric softener active having the formula 1,2-di(acyloxy)-3-trimethylammoniopropane chloride.
[0077] In another embodiment, the cationic surfactant is one or more softener quaternary ammonium compounds, e.g., C 12 ~C 22 Mono-alkyl quaternary ammonium compounds, C 12 ~C 22 Di-alkyl quaternary ammonium compounds, C 12 ~C 22 These include, but are not limited to, mono-alkylamine compounds, monoester quaternary ammonium compounds, diamide quaternary compounds, and combinations thereof.
[0078] Other active ingredients suitable for use as cationic surfactants include, for example, the reaction products of fatty acids and dialkylene triamines in a molar ratio of about 2:1, the reaction products comprising compounds of the formula: R 1 -C(O)-NH-R 2 -NH-R 3-NH-C(O)-R 1 In the formula, R 1 , R 2 is as defined above, and each R 3 is C 1~6 An example of these active ingredients is the reaction product of tallow acid, canola acid, or oleic acid with diethylenetriamine in a molecular ratio of about 2:1, the reaction product mixture containing N,N''-ditallowoyldiethylenetriamine, N,N''-dicanola-oyldiethylenetriamine, or N,N''-dioleoyldiethylenetriamine, respectively, of the formula: R 1 -C(O)-NH-CH2CH2-NH-CH2CH2-NH-C(O)-R 1 In the formula, R 2 and R 3 is a divalent ethylene group, R 1 is as defined above, and R 1 Wherein is the oleoyl group of commercially available oleic acid derived from vegetable or animal sources, acceptable examples of this structure include EMERSOL® 223LL or EMERSOL® 7021 available from Henkel Corporation.
[0079] Another active ingredient used as a cationic surfactant has the formula: [R 1 -C(O)-NR-R 2 -N(R)2-R 3 -NR-C(O)-R 1 ] + X - In the formula, R, R 1 , R 2 , R 3 and X - is defined above. An example of this active ingredient is a difatty amidoamine based softener having the formula: [R 1 -C(O)-NH-CH2CH2-N(CH3)(CH2CH2OH)-CH2CH2-NH-C(O)-R1 ] + CH3SO4 - In the formula, R 1 -C(O) is an oleoyl group, a soft tallow group, or a hydrogenated tallow group, available from Degussa under the trade names VARISOFT® 222LT, VARISOFT® 222, and VARISOFT® 110, respectively.
[0080] In a particularly preferred embodiment of the present disclosure, the majority of the surfactant in the flexible porous dissolvable solid sheet article is a diester quaternary ammonium (DEQA) compound, C 12 ~C 22 Mono / di-alkyl quaternary ammonium compounds, C 12 ~C 22 Mono-alkylamine compounds, C8-C12 with a weight average degree of ethoxylation of about 1 to about 20 18 cationic and / or nonionic surfactants selected from the group consisting of alkyl ethoxylated alcohols, alkyl ethoxylated alcohols, and combinations thereof, and each of the microcapsules preferably further comprises a cationic coating on its shell, the cationic coating being formed from a cationic polymer selected from the group consisting of polyvinylformamide, partially hydroxylated polyvinylformamide, polyvinylamine, polyethyleneimine, ethoxylated polyethyleneimine, cationically modified polysaccharides, and combinations thereof. Without being bound by any theory, it is believed that matching the surface charge of the microcapsules with the type of surfactant used in the solid sheet article may further help to reduce the risk of premature rupture / fracture of the microcapsules and preserve the structural integrity of such microcapsules.
[0081] Amphoteric surfactants suitable for use in the solid sheets of the present disclosure include those broadly described as derivatives of aliphatic secondary and tertiary amines, where the aliphatic radical may be straight or branched, one of the aliphatic substituents containing from about 8 to about 18 carbon atoms and one containing an anionic water-soluble group, such as carboxy, sulfonate, sulfate, phosphate, or phosphonate. Examples of compounds falling within this definition are sodium 3-dodecylaminopropionate, sodium 3-dodecylaminopropanesulfonate, sodium lauryl sarcosinate, N-alkyltaurines such as those prepared by reacting dodecylamine with sodium isethionate, and N-higher alkyl aspartic acids.
[0082] One category of amphoteric surfactants particularly suitable for incorporation into solid sheets having personal care applications (e.g., shampoos, face or body washes, etc.) includes alkyl amphoacetates such as lauroamphoacetate and cocoamphoacetate. The alkyl amphoacetates may be composed of monoacetates and diacetates. In some types of alkyl amphoacetates, the diacetate is an impurity or an unintended reaction product. The amount of alkyl amphoacetate in the solid sheets of the present disclosure may range from about 2% to about 40%, preferably from about 5% to about 30%, more preferably from about 10% to about 20%, based on the total weight of the solid sheet.
[0083] Suitable zwitterionic surfactants include those broadly described as derivatives of aliphatic quaternary ammonium, phosphonium and sulfonium compounds, in which the aliphatic radicals can be straight or branched chain, one of the aliphatic substituents containing from about 8 to about 18 carbon atoms and one containing an anionic group, such as a carboxy, sulfonate, sulfate, phosphate or phosphonate. Such suitable zwitterionic surfactants can be represented by the formula:
[0084] [ka] In the formula, R2 contains an alkyl, alkenyl, or hydroxyalkyl radical of about 8 to about 18 carbon atoms, 0 to about 10 ethylene oxide moieties, and 0 to about 1 glyceryl moiety; Y is selected from the group consisting of nitrogen, phosphorus, and sulfur atoms; R 3 is an alkyl or monohydroxyalkyl group containing from about 1 to about 3 carbon atoms, X is 1 when Y is a sulfur atom and is 2 when Y is a nitrogen or phosphorus atom, R 4 is an alkylene or hydroxyalkylene of about 1 to about 4 carbon atoms and Z is a radical selected from the group consisting of carboxylate, sulfonate, sulfate, phosphonate, and phosphate groups.
[0085] Other zwitterionic surfactants suitable for use herein include betaines including higher alkyl betaines such as cocodimethyl carboxymethyl betaine, cocoamidopropyl betaine, coco betaine, lauryl amidopropyl betaine, oleyl betaine, lauryl dimethyl carboxymethyl betaine, lauryl dimethyl alpha carboxyethyl betaine, cetyl dimethyl carboxymethyl betaine, lauryl bis-(2-hydroxyethyl) carboxymethyl betaine, stearyl bis-(2-hydroxypropyl) carboxymethyl betaine, oleyl dimethyl gamma carboxypropyl betaine, and lauryl bis-(2-hydroxypropyl) alpha carboxyethyl betaine. Sulfobetaines can be represented by cocodimethyl sulfopropyl betaine, stearyl dimethyl sulfopropyl betaine, lauryl dimethyl sulfoethyl betaine, lauryl bis-(2-hydroxyethyl) sulfopropyl betaine, and the like, and are represented by the RCONH(CH2)3 radical, where R is C 11 ~C 17 Amidobetaines and amidosulfobetaines, in which a radical (which is an alkyl) is attached to the nitrogen atom of the betaine, are also useful in the present invention.
[0086] Polymeric surfactants suitable for use in the solid sheet article compositions of the present disclosure include, but are not limited to, block copolymers of ethylene oxide and fatty alkyl residues, block copolymers of ethylene oxide and propylene oxide, hydrophobically modified polyacrylates, hydrophobically modified celluloses, silicone polyethers, silicone copolyol esters, diquaternary polydimethylsiloxanes, and co-modified amino / polyether silicones.
[0087] In a preferred embodiment, the surfactant comprises a blend of Group I and Group II surfactants. The surfactant blend of the present invention comprises one or more surfactants from Group I and one or more surfactants from Group II. Group I surfactants include anionic surfactants and Group II surfactants include amphoteric surfactants, zwitterionic surfactants, and combinations thereof. In one embodiment of the present invention, the ratio of Group I surfactants to Group II surfactants is about 95:5 to about 30:70. In another embodiment of the present invention, the ratio of Group I surfactants to Group II surfactants is about 85:15 to about 40:60. In yet another embodiment of the present invention, the ratio of Group I surfactants to Group II surfactants is about 70:30 to about 55:45.
[0088] Group I Surfactants The Group I surfactants of the present invention include one or more anionic surfactants. Suitable anionic surfactant components for use in the dissolvable articles herein include those known for use in hair care or other personal care shampoo compositions. The concentration of the anionic surfactant component in the composition should be sufficient to provide the desired cleaning and lathering performance, and ranges from about 6.5% to about 71% by weight of the dry solids of the Group I surfactant.
[0089] Anionic surfactants suitable for use in the present compositions include alkyl sulfates and alkyl ether sulfates. These materials have the formula ROSO3M and RO(C2H4O)xSO3M, respectively, where R is an alkyl or alkenyl of about 8 to about 18 carbon atoms, x is an integer having a value of 1 to 10, and M is a cation, such as ammonium, an alkanolamine, such as triethanolamine, a polyvalent metal, such as sodium and potassium, and a polyvalent metal cation, such as magnesium and calcium. Preferably, R has about 8 to about 18 carbon atoms, more preferably about 10 to about 16 carbon atoms, and even more preferably about 11 to about 14 carbon atoms, in both the alkyl and alkyl ether sulfates. The alkyl ether sulfates are typically made as the condensation product of ethylene oxide and a monohydric alcohol having about 8 to about 24 carbon atoms. The alcohol can be synthetic, or the alcohol can be derived from fats, such as coconut oil, palm kernel oil, tallow. Synthetic alcohols may include grades available from Shell Chemical Co. under the trademark NEODOL, namely, NEODOL 91 (C9-11 alcohol), NEODOL 23 (C12-13 alcohol), NEODOL 25 (C12-15 alcohol), NEODOL 45 (C14-15 alcohol), and NEODOL 135 (C11-C13-C15 alcohol). Lauryl alcohol and straight chain alcohols derived from coconut oil or palm kernel oil are preferred. Such alcohols are reacted with a molar ratio of ethylene oxide of about 0 to about 10, in one embodiment about 2 to about 5, and in another embodiment about 3, and the resulting mixture of molecular species having, for example, an average of 3 moles of ethylene oxide per mole of alcohol is sulfated and neutralized.
[0090] Other suitable anionic surfactants are the water-soluble salts of organosulfuric acid reaction products conforming to the formula [R1-SO3-M], where R1 is a straight or branched chain saturated aliphatic hydrocarbon radical having from about 8 to about 24, preferably from about 10 to about 18, carbon atoms, and M is a cation as described above.
[0091] Still other suitable anionic surfactants are reaction products of fatty acids esterified with isethionic acid and neutralized with sodium hydroxide, for example, the fatty acid is derived from coconut oil or palm kernel oil, for example, the fatty acid is the sodium or potassium salt of fatty acid amide of methyl tauride derived from coconut oil.Other similar anionic surfactants are described in U.S. Patent Nos. 2,486,921, 2,486,922, and 2,396,278.
[0092] Other anionic surfactants suitable for use in the compositions are succinates, examples of which include disodium N-octadecyl sulfosuccinate, disodium lauryl sulfosuccinate, diammonium lauryl sulfosuccinate, tetrasodium N-(1,2-dicarboxyethyl)-N-octadecyl sulfosuccinate, diamyl ester of sodium sulfosuccinate, dihexyl ester of sodium sulfosuccinate, and dioctyl ester of sodium sulfosuccinate.
[0093] Other suitable anionic surfactants include olefin sulfonates having from about 10 to about 24 carbon atoms. In addition to true alkene sulfonates and certain hydroxyalkane sulfonates, olefin sulfonates may contain small amounts of other materials, such as alkene disulfonates, depending on the reaction conditions, the ratio of reactants, the nature of the starting olefin and impurities in the olefin feedstock, and side reactions during the sulfonation process. Non-limiting examples of such alpha-olefin sulfonate mixtures are described in U.S. Pat. No. 3,332,880.
[0094] Another class of anionic surfactants suitable for use in the composition are the beta-alkyloxyalkanesulfonates. These surfactants conform to the formula:
[0095] [ka] In the formula, R1 is a straight chain alkyl group having about 6 to about 20 carbon atoms, R2 is a lower alkyl group having about 1 to about 3 carbon atoms, preferably 1 carbon atom, and M is a water-soluble cation as described above.
[0096] Additional anionic surfactants suitable for use in the compositions include ammonium lauryl sulfate, ammonium laureth sulfate, ammonium laureth-1 sulfate, ammonium laureth-2 sulfate, ammonium laureth-3 sulfate, triethanolamine lauryl sulfate, triethanolamine laureth sulfate, triethanolamine laureth-1 sulfate, triethanolamine laureth-2 sulfate, triethanolamine laureth-3 sulfate, monoethanolamine lauryl sulfate, monoethanolamine laureth sulfate, diethanolamine lauryl sulfate, diethanolamine laureth sulfate, sodium lauric monoglyceride sulfate, sodium lauryl sulfate, and laureth sulfate. sodium, potassium lauryl sulfate, potassium laureth sulfate, sodium lauryl sarcosinate, sodium lauroyl sarcosinate, lauryl sarcosine, cocoyl sarcosine, ammonium cocoyl sulfate, ammonium lauroyl sulfate, sodium cocoyl sulfate, sodium lauroyl sulfate, potassium cocoyl sulfate, potassium lauryl sulfate, monoethanolamine cocoyl sulfate, monoethanolamine lauryl sulfate, sodium tridecylbenzenesulfonate, sodium dodecylbenzenesulfonate, sodium cocoyl isethionate, ammonium decyl sulfate, sodium decyl sulfate, ammonium undecyl sulfate, and ammonium undecyl sulfate, and combinations thereof.
[0097] In one embodiment of the invention, one or more of the surfactants are alkyl sulfates. In one embodiment, the one or more alkyl sulfates have an average molar number of ethoxylation of about 0.0 to about 1.9, in another embodiment, the one or more alkyl sulfates have an average molar number of ethoxylation of about 0.0 to about 1.5, and in yet another embodiment, the one or more alkyl sulfates have an average molar number of ethoxylation of about 0.0 to about 1.0. In one embodiment, the one or more alkyl sulfates include an ammonium counterion. Suitable examples of such surfactants with ammonium counterions include, but are not limited to, ammonium lauryl sulfate, ammonium laureth-1 sulfate, ammonium laureth-2 sulfate, and combinations thereof.
[0098] In one embodiment, the one or more Group I surfactants are selected from alkyl sulfates having the structure:
[0099] [ka] In the formula, R 1 is selected from the group consisting of substituted or unsubstituted straight or branched chain alkyl or unsaturated alkyl systems containing an average of 9.0 to 11.9 carbon atoms, C-bonded monovalent substituents selected from the group consisting of: 2 is selected from the group consisting of C-bonded divalent linear or branched alkyl systems containing 2 to 3 carbon atoms; M +is a monovalent counterion selected from sodium, ammonium, or protonated triethanolamine, and x is 0.0 to 3.0. In one embodiment, one or more of the alkyl sulfate surfactants according to the above structure comprises an average number of moles of ethoxylation of about 0.0 to about 1.9, in another embodiment, the alkyl sulfate surfactant according to the above structure comprises an average number of moles of ethoxylation of about 0.0 to about 1.5, and in yet another embodiment, the alkyl sulfate surfactant according to the above structure comprises an average number of moles of ethoxylation of about 0.0 to about 1.0. Suitable examples include ammonium decyl sulfate, sodium decyl sulfate, ammonium undecyl sulfate, sodium undecyl sulfate, triethanolamine decyl sulfate, or triethanolamine undecyl sulfate. In one embodiment, the anionic surfactant of the present invention comprises ammonium undecyl sulfate.
[0100] Group II Surfactants The Group II surfactants of the present invention include one or more amphoteric surfactants, zwitterionic surfactants, and / or combinations thereof. Suitable amphoteric or zwitterionic surfactants for use in the compositions herein include those known for use in hair care or other personal care cleansing. The concentration of such amphoteric, zwitterionic surfactants, and / or combinations thereof ranges from about 1.0% to about 52.5% by weight of dry solids. Non-limiting examples of suitable zwitterionic or amphoteric surfactants are described in U.S. Pat. Nos. 5,104,646 (Bolich Jr. et al.) and 5,106,609 (Bolich Jr. et al.).
[0101] Suitable amphoteric surfactants for use in the present compositions are well known in the art and include surfactants broadly described as derivatives of aliphatic secondary and tertiary amines, the aliphatic groups of which can be straight or branched, one of the aliphatic substituents containing from about 8 to about 18 carbon atoms and one containing an anionic group such as carboxy, sulfonate, sulfate, phosphate, or phosphonate. Suitable examples of such amphoteric surfactants include sodium cocaminopropionate, sodium cocaminodipropionate, sodium cocoamphoacetate, sodium cocoamphohydroxypropylsulfonate, sodium cocoamphopropionate, sodium cornamphopropionate, sodium lauraminopropionate, sodium lauroamphoacetate, sodium lauroamphohydroxypropylsulfonate, sodium lauroamphopropionate, sodium cornamphopropionate.cornamphopropionate), sodium lauriminodipropionate, ammonium cocaminopropionate, ammonium cocaminodipropionate, ammonium cocoamphoacetate, ammonium cocoamphohydroxypropylsulfonate, ammonium cocoamphopropionate, ammonium cornamphopropionate, ammonium lauraminopropionate, ammonium lauroamphoacetate, ammonium lauroamphohydroxypropylsulfonate, ammonium lauroamphopropionate, ammonium cornamphopropionate, ammonium lauraminodipropionate, triethanolamine cocaminopropionate, triethanolamine cocaminodipropionate, triethanolamine cocoamphoacetate Triethanolamine, Triethanolamine Cocoampho Hydroxypropyl Sulfonate, Triethanolamine Cocoamphopropionate, Triethanolamine Comamphopropionate, Triethanolamine Lauraminopropionate, Triethanolamine Lauroamphoacetate, Triethanolamine Lauroampho Hydroxypropyl Sulfonate, Triethanolamine Lauroamphopropionate, Triethanolamine Cornamphopropionate, Triethanolamine Lauraminodipropionate, Cocoamphodipropionic Acid, Disodium Caproamphodiacetate, Disodium Caproamphodipropionate, Disodium Capryloamphodiacetate, Disodium Capryloamphodipropionate capryloamphodipriopionate), disodium cocoamphocarboxyethyl hydroxypropyl sulfonate, disodium cocoamphodiacetate, disodium cocoamphodipropionate, disodium dicarboxyethyl cocopropylenediamine, disodium laureth-5 carboxyamphodiacetate, disodium lauriminodipropionate, disodium lauroamphodiacetate, disodium lauroamphodipropionate, disodium oleoamphodipropionate, PPG-2-isodeceth-7 carboxyamphodiacetate, lauraminopropionic acid, lauroamphodipropionic acid, lauryl aminopropyl glycine, lauryl diethylenediaminoglycine, and combinations thereof.
[0102] In one embodiment, the amphoteric surfactant is a surfactant according to the following structure:
[0103] [ka] In the formula, R1 is a C-linked monovalent substituent selected from the group consisting of substituted alkyls containing 9-15 carbon atoms, unsubstituted alkyls containing 9-15 carbon atoms, linear alkyls containing 9-15 carbon atoms, branched alkyls containing 9-15 carbon atoms, and unsaturated alkyls containing 9-15 carbon atoms; R2, R3, and R4 are each independently selected from the group consisting of C-linked divalent linear alkyls containing 1-3 carbon atoms, and C-linked divalent branched alkyls containing 1-3 carbon atoms; and M+ is a monovalent counterion selected from the group consisting of sodium, ammonium, and protonated triethanolamine. Specific examples of suitable surfactants include sodium cocoamphoacetate, sodium cocoamphodiacetate, sodium lauroamphoacetate, sodium lauroamphodiacetate, ammonium lauroamphoacetate, ammonium cocoamphoacetate, triethanolamine lauroamphoacetate, and triethanolamine cocoamphoacetate.
[0104] Zwitterionic surfactants suitable for use in the compositions are well known in the art and include surfactants broadly described as derivatives of aliphatic quaternary ammonium, phosphonium, and sulfonium compounds, where the aliphatic radicals may be straight or branched chain, one of the aliphatic substituents contains from about 8 to about 18 carbon atoms, and one contains an anionic group, such as a carboxy, sulfonate, sulfate, phosphate, or phosphonate. Suitable zwitterionic surfactants include, but are not limited to, cocamidoethyl betaine, cocamidopropylamine oxide, cocamidopropyl betaine, cocamidopropyl dimethylamino hydroxypropyl hydrolyzed collagen, cocamidopropyl dimonium hydroxypropyl hydrolyzed collagen, cocamidopropyl hydroxysultaine, cocobetaine amide amphopropionate, coco-betaine, coco-hydroxysultaine, coco / oleamidopropyl betaine, coco-sultaine, lauramidopropyl betaine, lauryl betaine, lauryl hydroxysultaine, lauryl sultaine, and combinations thereof.
[0105] 4. Plasticizers The flexible porous dissolvable solid sheet articles of the present disclosure may also include a plasticizer, preferably in an amount ranging from about 1% to about 65%, preferably from about 10% to about 60%, more preferably from about 15% to about 55%, even more preferably from about 20% to about 50%, and most preferably from about 22% to about 40%, based on the total weight of the solid sheet article. Accordingly, the wet premix used to form such solid sheet articles may include from about 0.1% to about 50%, preferably from about 1% to about 40%, more preferably from about 5% to about 30%, even more preferably from about 8% to about 25%, and most preferably from about 10% to about 20% of a plasticizer, based on the weight of the wet premix.
[0106] Plasticizers suitable for use in the present disclosure include, for example, polyols, copolyols, polycarboxylic acids, polyesters, dimethicone copolyols, and the like.
[0107] Examples of useful polyols include, but are not limited to, glycerin, diglycerin, ethylene glycol, polyethylene glycol (especially 200-600), propylene glycol, butylene glycol, pentylene glycol, glycerol derivatives (such as propoxylated glycerol), glycidol, cyclohexanedimethanol, hexanediol, 2,2,4-trimethylpentane-1,3-diol, pentaerythritol, urea, sugar alcohols (such as sorbitol, mannitol, lactitol, xylitol, maltitol, and other mono- and polyhydric alcohols), mono-, di-, and oligo-saccharides (such as fructose, glucose, sucrose, maltose, lactose, high fructose corn syrup solids, and dextrins), ascorbic acid, sorbates, ethylene bisformamide, amino acids, and the like.
[0108] Examples of polycarboxylic acids include, but are not limited to, citric acid, maleic acid, succinic acid, polyacrylic acid, and polymaleic acid.
[0109] Examples of suitable polyesters include, but are not limited to, glycerol triacetate, acetylated monoglyceride, diethyl phthalate, triethyl citrate, tributyl citrate, acetyl triethyl citrate, acetyl tributyl citrate.
[0110] Examples of suitable dimethicone copolyols include, but are not limited to, PEG-12 dimethicone, PEG / PPG-18 / 18 dimethicone, and PPG-12 dimethicone.
[0111] Other suitable plasticizers include alkyl and aryl phthalates; naphthalates; lactates (e.g., sodium, ammonium, and potassium salts); Sorbeth-30; urea; lactic acid; pyrrolidone carboxylic acid (PCA); sodium hyaluronate or hyaluronic acid; soluble collagen; modified proteins; monosodium L-glutamate; alpha and beta hydroxyl acids, such as glycolic acid, lactic acid, citric acid, maleic acid, and salicylic acid; glyceryl polymethacrylate; polymeric plasticizers, such as polyquaternium; proteins and amino acids, such as glutamic acid, aspartic acid, and lysine; hydrogenated starch hydrolysates; and other low molecular weight esters (e.g., C2-C 10 and any other water soluble plasticizers known to those of ordinary skill in the food and plastics industries; and mixtures thereof.
[0112] Particularly preferred examples of plasticizers include glycerin, ethylene glycol, polyethylene glycol, propylene glycol, and mixtures thereof. The most preferred plasticizer is glycerin. The presence of a preferred plasticizer, such as glycerin, in the solid sheet may further provide wrinkle prevention benefits. In particular, when the solid sheet article includes a preferred amount of glycerin (e.g., 22% to 40% based on the total weight of the solid sheet), the wrinkle prevention effect may be even more significant.
[0113] 5. Other ingredients In addition to the above-mentioned formulation ingredients, such as microcapsules, water-soluble polymers, surfactants, and plasticizers, the flexible porous dissolvable solid sheet article of the present disclosure may include one or more additional formulation ingredients depending on its intended use. Such one or more additional ingredients may be selected from the group consisting of fabric care actives, dishwashing actives, hard surface cleaning actives, beauty and / or skin care actives, personal cleansing actives, hair care actives, oral care actives, feminine care actives, baby care actives, bittering agents, and any combination thereof. In a preferred embodiment, the solid sheet of the present disclosure may include a bittering agent.
[0114] Suitable fabric care actives include, but are not limited to, organic solvents (straight or branched chain lower C1-C8 alcohols, diols, glycerol, or glycols; lower amine solvents such as C1-C4 alkanolamines, and mixtures thereof; more specifically 1,2-propanediol, ethanol, glycerol, monoethanolamine, and triethanolamine), carriers, hydrotropes, builders, chelating agents, dispersants, enzymes and enzyme stabilizers, catalytic materials, bleaches (including photobleaches) and bleach activators, perfumes (including encapsulated perfumes or perfume microcapsules), colorants (such as pigments and dyes, including hueing dyes), brighteners, dye transfer inhibitors, clay soil removal / anti-redeposition agents, structurants, rheology modifiers, suds suppressors, processing aids, fabric softeners, antimicrobial agents, and the like.
[0115] Suitable hair care actives include Class II moisture conditioning agents for frizz reduction (salicylic acid and derivatives, organic alcohols, and esters), cationic surfactants (especially those having a solubility in water at 25° C., preferably less than 0.5 g / 100 g water, more preferably less than 0.3 g / 100 g water), high melting point fatty compounds (e.g., fatty alcohols, fatty acids, and mixtures thereof, having a melting point of 25° C. or more, preferably 40° C. or more, more preferably 45° C. or more, and even more preferably 50° C. or more), silicone compounds, conditioning agents (such as those available under the trade name Peptein from Hormel), and the like. 2000, hydrolyzed collagen, vitamin E under the trade name Emix-d available from Eisai, panthenol available from Roche, panthenyl ethyl ether available from Roche, hydrolyzed keratin, proteins, plant extracts, and nutrients), preservatives (such as benzyl alcohol, methylparaben, propylparaben, and imidazolidinyl urea), pH adjusters (such as citric acid, sodium citrate, succinic acid, phosphoric acid, sodium hydroxide, sodium carbonate, and the like), salts (such as potassium acetate and sodium chloride), colorants, fragrances or fragrances, sequestering agents (such as disodium ethylenediaminetetraacetate), ultraviolet and infrared screening and absorbing agents (such as octyl salicylate), hair bleaches, hair perms, hair fixatives, anti-dandruff agents, antibacterial agents, hair growth agents or supplements, co-solvents or other additional solvents, and the like.
[0116] Suitable cosmetic and / or skin care actives include those approved for use in cosmetics and described in references such as the CTFA Cosmetic Ingredient Handbook, Second Edition, The Cosmetic, Toiletries, and Fragrance Association, Inc. 1988, 1992. Further non-limiting examples of suitable cosmetic and / or skin care actives include preservatives, fragrances or fragrances, colorants or dyes, thickeners, moisturizers, emollients, pharmaceutical actives, vitamins or nutrients, sunscreens, deodorants, sensates, botanical extracts, nutrients, astringents, cosmetic particles, absorbent particles, fibers, anti-inflammatory agents, skin lightening agents, skin toning agents (which function to improve overall skin tone and may include vitamin B3 compounds, sugar amines, hexamidine compounds, salicylic acid, hexylresorcinol, and 1,3-dihydroxy-4-alkylbenzenes such as retinoids), skin tanning agents, exfoliants, moisturizers, enzymes, antioxidants, free radical scavengers, anti-wrinkle actives, anti-acne agents, acids, bases, minerals, suspending agents, pH adjusters, pigment particles, antibacterial agents, insect repellents, shaving lotions, co-solvents or other additional solvents, and the like.
[0117] Suitable bittering agents include denatonium salts or derivatives thereof. In one embodiment, the bittering agent is a denatonium salt selected from the group consisting of denatonium chloride, denatonium citrate, denatonium saccharide, denatonium carbonate, denatonium acetate, denatonium benzoate, and mixtures thereof. In one embodiment, the solid sheet comprises a first denatonium salt and the coating composition comprises a second denatonium salt different from the first denatonium salt.
[0118] A particularly preferred bittering agent is denatonium benzoate, also known as phenylmethyl-[2-[(2,6-dimethylphenyl)amino]-2-oxoethyl]-diethylammonium benzoate (CAS number 3734-33-6), which is commercially available as BITREX® and is available from Macfarlan Smith, Edinburgh, Scotland, UK.
[0119] In some embodiments, the bittering agent is a natural bittering substance. In some embodiments, the bittering agent has a bitterness value of about 1000 to about 200000. In some embodiments, the bittering agent is a natural bittering substance having a bitterness value of about 1000 to about 200000, and the natural bittering substance is selected from the group consisting of glycosides, isoprenoids, alkaloids, amino acids, and mixtures thereof. For example, suitable bittering agents include quercetin (3,3',4',5,7-pentahydroxyflavone), naringin (4',5,7-trihydroxyflavanone-7-rhamnoglucoside), aucubin, amarogentin, dihydrofoliamentin, gentiopicroside, gentiopicrin, swerthiamarin, sweroside, gentioflavoside, centauroside, methiafoline, harpagoside, centapicrin, cylysin, condurandin, absinthin, artavsin, cunisin, lactucin, and lactuarazine. Also included are copicrin, salonitenolide, a-thujone, β-thujone, desoxylimonene, limonin, itchangin, isoobacunic acid, obacunone, obacunic acid, nomilin, itchangin, nomilinic acid, malvin, pramalvin, carnosol, carnosic acid, quasin, quinine hydrochloride, quinine sulfate, quinine dihydrochloride, columbine, caffeine, threonine, methionine, phenylalanine, tryptophan, arginine, histidine, valine, aspartic acid, sucrose octaacetate, and mixtures thereof. Other suitable bittering agents include quinine disulfate and hop extracts (e.g., humulone).
[0120] The solid sheet articles of the present disclosure may comprise from about 0.00001% to about 1%, or from about 0.0001% to about 0.5%, or from about 0.001% to about 0.25%, or from about 0.01% to about 0.1% of a bittering agent, based on the weight of the solid sheet. In some embodiments, the solid sheet article comprises a sufficient amount of a bittering agent to provide a bitter taste.
[0121] The solid sheet articles of the present disclosure may further comprise other optional ingredients as are known or useful for use in compositions, provided that such optional materials are compatible with the selected essential materials described herein or do not unduly impair product performance.
[0122] Non-limiting examples of product type embodiments that may be formed by the solid sheet articles of the present disclosure include laundry detergent products, fabric softener products, hand washing products, hair shampoos or other hair treatment products, body cleansing products, shaving preparation products, dishwashing products, personal care substrates containing pharmaceutical or other skin care actives, moisturizing products, sunscreen products, beauty or skin care products, deodorant products, oral care products, feminine cleaning products, baby care products, fragrance-containing products, and the like.
[0123] III. Methods for Making Solid Sheets The present disclosure provides a new and improved method for making flexible porous dissolvable solid sheets having an OCF structure and containing direct-added PMC or other active-containing microcapsules therein, the method comprising the steps of: (a) providing a wet premix containing raw materials (e.g., microcapsules, water-soluble polymer, surfactant, and optionally plasticizer, and other active formulation ingredients) dissolved or dispersed in water or a suitable solvent, the wet premix being heated at about 40° C. and 1 s. -1The method includes the steps of: (a) providing a wet premix characterized by a viscosity of about 1,000 cps to about 25,000 cps measured at 1000° C.; (b) aerating the wet premix (e.g., by introducing a gas into the wet slurry) to form an aerated wet premix characterized by a low density of about 0.05 to about 0.5 g / mL; (c) forming the aerated wet premix into a sheet; and (d) drying the formed sheet at a temperature of 70° C. to 200° C. for a drying time of 1 minute to 60 minutes to form a solid sheet article of the present disclosure. Preferably, the sheet formed by the aerated wet premix has opposing first and second sides, and drying of the so-formed sheet is performed along a heating direction that forms a decreasing temperature gradient from the first side to the second side of the formed sheet, the heating direction being substantially offset from the direction of gravity for more than half of the drying time, i.e., the drying step is performed under heating along a mostly "anti-gravity" heating direction. Such a primarily "anti-gravity" heating orientation can be achieved by a variety of means, including but not limited to bottom conduction heating / drying configurations and rotating drum heating / drying configurations.
[0124] The process steps and conditions for forming the flexible porous dissolvable solid sheet articles of the present disclosure, i.e., flexible porous dissolvable solid sheet articles having an OCF structure and containing PMC and / or other active-containing microcapsules therein, are described in detail below.
[0125] Step (A): Preparation of Wet Premix The wet premix of the present disclosure is generally prepared by mixing the raw materials of interest, including microcapsules, water-soluble polymers, surfactants, plasticizers, and / or other compounding ingredients, with a sufficient amount of water or another solvent in a premix tank. The wet premix can be formed using a mechanical mixer. Mechanical mixers useful herein include, but are not limited to, a turbine with pitched blades or a MAXBLEND mixer (Sumitomo Heavy Industries).
[0126] In a preferred but not required embodiment of the present disclosure, the microcapsules are provided in a slurry form having a substantial amount of water (e.g., greater than 20%, preferably greater than 30%, more preferably greater than 50%). The microcapsule slurry can be formed by the following method. a) preparing a first solution, which may contain 20%-90%, 40%-80%, or even 60%-80% water based on the total solution weight of the first emulsifier and the first resin, wherein the ratio of the first emulsifier to the first resin is 0.1:0-10:0, about 0.1:1-10:1, 0.5:1-3:1, or even 0.8:1-1.1:1; b) preparing a second solution that may contain about 20% to about 95% water based on the total solution weight of the second emulsifier and the second resin, wherein the ratio of the second emulsifier to the second resin is from 0:1 to about 3:1, 0.04:1 to 0.2:1, or even 0.05:1 to 0.15:1; c) combining a benefit agent (e.g., fragrance) with the first solution to form a first composition; d) emulsifying the first composition; e) combining the first composition with the second solution to form a second composition and, optionally, combining any processing aids with the second composition, where the first composition and the second solution can be combined in any order, although in one embodiment the second solution is added to the first composition or the second solution is combined with the first composition simultaneously; f) mixing the second composition for at least 15 minutes, at least 1 hour, or even for 4 hours to 100 hours at a temperature of heat between 25° C. and 100° C., between 45° C. and 90° C., or even between 50° C. and 80° C., and optionally combining any processing aids with the second composition; g) during or after step f), optionally combining any scavenger material, structurant, and / or anti-agglomerating agent with said second composition, such materials may be combined in any order, although in one embodiment the scavenger material is combined first, any structurant second, followed by the anti-agglomerating agent; h) optionally spray drying said second composition.
[0127] In one or more aspects of the microcapsule preparation method, the first and second resins may comprise a reaction product of an aldehyde and an amine, with suitable aldehydes including formaldehyde. Suitable amines include melamine, urea, benzoguanamine, glycoluril, and mixtures thereof. Suitable melamines include methylolmelamine, methylated methylolmelamine, iminomelamine, and mixtures thereof. Suitable ureas include dimethylolurea, methylated dimethylolurea, urea-resorcinol, and mixtures thereof.
[0128] In one or more aspects of the method, the first and second emulsifiers may comprise a moiety selected from the group consisting of carboxy, hydroxyl, thiol, amine, amide, and combinations thereof. In one aspect, the emulsifiers may have a pKa less than 5, preferably greater than 0 and less than 5. Emulsifiers include acrylic acid-alkyl acrylate copolymers, poly(acrylic acid), polyoxyalkylene sorbitan fatty acid esters, polyalkylene-co-carboxyanhydrides, polyalkylene-co-maleic anhydride, poly(methyl vinyl ether-co-maleic anhydride), poly(propylene-co-maleic anhydride), poly(butadiene)-co-maleic anhydride), and poly(vinyl acetate-co-maleic anhydride), polyvinyl alcohol, polyalkylene glycols, polyoxyalkylene glycols, and mixtures thereof.
[0129] In one or more aspects of the method, the pH of the first and second solutions may be controlled such that the pH of the first and second solutions is between about 3.0 and 7.0.
[0130] In one or more embodiments of the method, during step f.), between 0% and 10%, 1% and 5%, or even 2% and 4% of a salt, based on the total weight of the second composition, comprising an anion and a cation, the anion being selected from the group consisting of chloride, sulfate, phosphate, nitrate, polyphosphate, citrate, maleate, fumarate, and mixtures thereof, and the cation being selected from the group consisting of Group IA elements of the periodic table, Group IIA elements of the periodic table, ammonium cations, and mixtures thereof, preferably sodium sulfate, may be combined with the second composition.
[0131] In one or more embodiments of the method, any of the above mentioned processing parameters may be combined.
[0132] Suitable equipment for use in the methods disclosed herein include continuous stirred tank reactors, homogenizers, turbine agitators, recirculation pumps, paddle mixers, plow shear mixers, ribbon blenders, vertical shaft granulators and drum mixers, both in batch mode, and spray dryers and extruders, where applicable, in continuous process configurations. Such equipment is available from Lodige GmbH (Paderborn, Germany), Littleford Day, Inc. (Florence, Kentucky, USA), Forberg AS (Larvik, Norway), Glatt Ingenieurtechnik GmbH (Weimar, Germany), Niro (Soeborg, Denmark), Hosokawa Bepex Corp. (Minneapolis, Minnesota, USA), and Arde Barinco (New Jersey, USA).
[0133] Such a microcapsule-containing slurry is mixed with other raw materials (e.g., water-soluble polymers, surfactants, plasticizers, and / or other formulation ingredients) and a sufficient amount of water or another solvent in a premix tank to form the wet premix described above.
[0134] In this disclosure, 40° C. and 1s -1 It is particularly important to control the viscosity of the wet premix so that it is within a predetermined range of about 1,000 cps to about 25,000 cps when measured at 40°C. The viscosity of the wet premix significantly affects the pore expansion and pore opening of the aerated premix during the subsequent drying step, and wet premixes with different viscosities may form flexible porous dissolvable solid sheets of very different foam structures. On the other hand, if the wet premix is too thick / too viscous (e.g., at 40°C and 1s), the viscosity of the wet premix may be too high. -1 Aeration of such wet premixes may become more difficult if the wet premix is too thin / stretchy (e.g., having a viscosity of more than about 25,000 cps as measured at 40° C. and 1 s). More importantly, interstitial liquid drainage from the thin film cell surfaces into the plateau boundaries of the three-dimensional foam during the subsequent drying step may be adversely affected or significantly restricted. Interstitial liquid drainage during drying is believed to be important to allow pore expansion and pore opening in the aerated wet premix during the subsequent drying step. As a result, the flexible porous dissolvable solid sheet so formed may have significantly smaller pores and lower interconnectivity between the pores (i.e., more "closed" pores than open pores), which makes it difficult for water to enter and exit such sheets. On the other hand, if the wet premix is too thin / stretchy (e.g., having a viscosity of more than about 25,000 cps as measured at 40° C. and 1 s), the aeration of such wet premixes may become more difficult if the wet premix is too thin / stretchy (e.g., having a viscosity of more than about 25,000 cps as measured at 40° C. and 1 s). -1 If the aerated wet premix has a viscosity of less than about 1,000 cps as measured by aerobic dynamics (e.g., 1000 psi), the aerated wet premix may not be stable enough, i.e., air bubbles may quickly burst, collapse, or coalesce in the wet premix after aeration and before drying. As a result, the resulting solid sheet may be much less porous and denser than desired.
[0135] In one embodiment, the viscosity of the wet premix is 40° C. and 1 s-1 The viscosity value of the premix is measured using a Malvern Kinexus Lab+ rheometer (CP1 / 50 SR3468 SS) with a cone and plate geometry at a gap width of 0.054 mm, a temperature of 40° C., and a shear rate of 1.0 reciprocal seconds for 360 seconds.
[0136] In a preferred, but not required, embodiment, the solid of interest is present in the wet premix at a concentration of about 15% to about 70%, preferably about 20% to about 50%, more preferably about 25% to about 45%, based on the total weight of the wet premix. The percent solids content is the sum of the weight percent based on the weight of the total processed mixture of all solid, semi-solid, and liquid components, excluding any appreciably volatile substances such as water and low boiling alcohols. On the other hand, if the solids content in the wet premix is too high, the viscosity of the wet premix may increase to a level that inhibits or adversely affects interstitial liquid drainage and prevents the formation of the desired primarily open-celled porous solid structure as described herein. On the other hand, if the solids content in the wet premix is too low, the viscosity of the wet premix may decrease to a level that causes bubble bursting / collapse / coalescence and increased percent shrinkage of the pore structure during drying, resulting in a solid sheet with significantly less porosity and density.
[0137] Of the solids of interest in the wet premix of the present disclosure, there may be present, based on the total weight of the solids, from about 0.1% to about 12% microcapsules, 1% to about 75% surfactant, from about 0.1% to about 25% water soluble polymer, and optionally from about 0.1% to about 25% plasticizer. Other active or benefit agents may also be added to the premix.
[0138] Optionally, the wet premix is quickly preheated prior to and / or during the aeration process at a temperature above ambient temperature, but below any temperature that would cause decomposition of the components therein. In one embodiment, the wet premix is maintained at an elevated temperature in the range of about 40°C to about 100°C, preferably about 50°C to about 95°C, more preferably about 60°C to about 90°C, and most preferably about 75°C to about 85°C. In one embodiment, optional continuous heating is utilized prior to the aeration step. Additionally, additional heat can be added during the aeration process to challenge and maintain the wet premix at such elevated temperatures. This can be accomplished by conductive heating from one or more surfaces, injection of steam, or other treatment means. It is believed that the act of preheating the wet premix prior to and / or during the aeration step may provide a means of reducing the viscosity of wet premixes containing higher percentages of solids in order to improve the introduction of air bubbles into the mixture and the formation of the desired solid sheet. Achieving a higher percentage of solids is desirable as it may reduce the overall energy requirements of drying. Thus, increasing the percent solids may result in a decrease in water concentration content and an increase in viscosity. As mentioned above, a wet premix with too high a viscosity is undesirable in the practice of the present disclosure. Preheating effectively counteracts such viscosity, thereby allowing the production of fast dissolving sheets even when using premixes with high solids content.
[0139] Step (B): Aeration of the Wet Premix Aeration of the wet premix is performed to introduce a sufficient amount of air bubbles into the wet premix to subsequently form an OCF structure therein upon drying. After being fully aerated, the wet premix is characterized by a density significantly lower than that of a non-aerated wet premix (which may contain a few inadvertently trapped air bubbles) or a poorly aerated wet premix (which may contain some air bubbles, but at a very low volumetric percentage and with significantly larger bubble sizes). Preferably, the aerated wet premix has a density in the range of about 0.05 g / mL to about 0.5 g / mL, preferably about 0.08 g / mL to about 0.4 g / mL, more preferably about 0.1 g / mL to about 0.35 g / mL, even more preferably about 0.15 g / mL to about 0.3 g / mL, and most preferably about 0.2 g / mL to about 0.25 g / mL.
[0140] Aeration can be achieved by either physical or chemical means in the present disclosure. In one embodiment, it can be achieved by introducing gas into the wet premix through mechanical agitation, for example, by using any suitable mechanical processing means, including, but not limited to, rotor-stator mixers, planetary mixers, pressurized mixers, non-pressurized mixers, batch mixers, continuous mixers, semi-continuous mixers, high shear mixers, low shear mixers, submerged scourers, or any combination thereof. In another embodiment, it can be achieved through chemical means, for example, using a chemical blowing agent to provide gas formation in situ via chemical reaction of one or more components, including the formation of carbon dioxide (CO2 gas) by the foaming system.
[0141] In a particularly preferred embodiment, it has been found that aeration of the wet premix can be cost-effectively achieved by using a continuous pressurized aerator or mixer that is conventionally utilized in the food industry in the manufacture of marshmallows. The continuous pressurized mixer serves to homogenize or aerate the wet premix, resulting in a highly uniform and stable foam structure with uniform cell size. The unique design of the high shear rotor / stator mixing head can result in uniform cell size in the layer of open cell foam. Suitable continuous pressurized aerators or mixers include Morton whisks (Morton Machine Co., Motherwell, Scotland), Oakes continuous automatic mixers (ETOakes Corporation, Hauppauge, New York), Fedco continuous mixers (Peerless Group, Sidney, Ohio), Mondo (Haas-Mondomix BV, Netherlands), Aeros (Aeros Industrial Equipment Co., Ltd., Guangdong Province, China), and Preswhip (Hosokawa Micron Group, Osaka, Japan). For example, an Aeros A20 continuous aerator can be operated at a feed pump speed setting of about 300-800 (preferably about 500-700) with a mix head speed setting of about 300-800 (preferably about 400-600), with an air flow rate of about 50-150 (preferably 60-130, more preferably 80-120), respectively. In another example, an Oakes continuous automated mixer can be operated at a mix head speed setting of about 10-30 rpm (preferably about 15-25 rpm, more preferably about 20 rpm), with an air flow rate of about 10-30 liters / hour (preferably about 15-25 L / hour, more preferably about 19-20 L / hour).
[0142] In another particular embodiment, aeration of the wet premix can be achieved by using a rotary bar that is part of the rotary drum dryer, more specifically, a component of the feed trough in which the wet premix is stored before being coated and dried on the heated exterior surface of the drum dryer. The rotary bar is typically used to agitate the wet premix to prevent phase separation or settling in the feed trough during the waiting time before being coated on the heated rotary drum of the drum dryer. In the present disclosure, such a rotary bar can be operated at a rotation speed ranging from about 150 to about 500 rpm, preferably from about 200 to about 400 rpm, more preferably from about 250 to about 350 rpm, to provide sufficient mechanical agitation necessary to mix the wet premix at the air interface and achieve the desired aeration of the wet premix.
[0143] As mentioned above, the wet premix can be maintained at an elevated temperature during the aeration process to tailor the viscosity of the wet premix for optimized aeration and controlled drainage during drying. For example, when aeration is accomplished by using a rotating bar on a rotating drum, the aerated wet premix in the feed trough is typically maintained at about 60° C. during the initial aeration by the rotating bar (while the rotating drum is stationary), and then heated to about 70° C. when the rotating drum is heated and begins to rotate.
[0144] The bubble size of the aerated wet premix helps achieve uniform layers within the OCF structure of the resulting solid sheet. In one embodiment, the bubble size of the aerated wet premix is from about 5 to about 100 micrometers, and in another embodiment, the bubble size is from about 20 micrometers to about 80 micrometers. The uniformity of the bubble size allows the resulting solid sheet to have a consistent density.
[0145] Step (C): Sheet formation After sufficient aeration, the aerated wet premix forms one or more sheets having opposing first and second surfaces. The sheet forming process can be carried out in any suitable manner, for example, by extrusion, casting, molding, vacuum forming, pressing, printing, coating, etc. More specifically, the aerated wet premix can be formed into a sheet by (i) casting it into a shallow cavity or tray or a specially designed sheet mold, (ii) extruding it onto a continuous belt or screen of a dryer, and (iii) coating it onto the exterior surface of a rotary drum dryer. Preferably, the support surface on which the sheet is formed is formed of or coated with a corrosion-resistant, non-interacting and / or non-stick material, such as metal (e.g., steel, chrome, etc.), TEFLON®, polycarbonate, NEOPRENE®, HDPE, LDPE, rubber, glass, etc.
[0146] Preferably, the formed sheet of aerated wet premix has a thickness in the range of 0.5 mm to 4 mm, preferably 0.6 mm to 3.5 mm, more preferably 0.7 mm to 3 mm, even more preferably 0.8 mm to 2 mm, and most preferably 0.9 mm to 1.5 mm. Controlling the thickness of such a formed sheet of aerated wet premix can be important to ensure that the resulting solid sheet has the desired OCF structure. If the formed sheet is too thin (e.g., less than 0.5 mm thick), many of the trapped air bubbles in the aerated wet premix will expand during the subsequent drying step to form through-holes that extend through the entire thickness of the resulting solid sheet. Such through-holes, if too numerous, can seriously impair both the overall structural integrity and aesthetic appearance of the sheet. If the formed sheet is too thick, it will not only take longer to dry, but will also result in a solid sheet with a larger pore size variation between different regions (e.g., top, middle, and bottom regions) along its thickness. This is because the longer the drying time, the more unbalanced forces may be created by bubble bursting / collapse / coalescence, liquid drainage, pore expansion, pore opening, water evaporation, etc. Additionally, multiple layers of relatively thin sheets can be assembled into three-dimensional structures of greater thickness to provide a desired cleaning or other effect, while providing sufficient pore structure for rapid dissolution and ensuring efficient drying within a relatively short drying time.
[0147] Step (D): Drying under antigravity heat During the drying step of the sheet making method according to the present disclosure, the OCF structure is formed under the simultaneous mechanisms of water evaporation, bubble collapse, interstitial liquid drainage from the thin film bubble surfaces into the plateau boundaries between the bubbles (creating openings between the bubbles to form open cells), and premix solidification. Various process conditions can affect these mechanisms, such as, for example, solids content in the wet premix, viscosity of the wet premix, gravity, and drying temperature, as well as the need to balance such process conditions to achieve controlled drainage to form the desired OCF structure.
[0148] In addition to the above-mentioned processing conditions, it was a surprising and unexpected discovery of the present disclosure that the direction of the thermal energy used during the drying process (i.e., heating direction) can also have a significant effect on the resulting OCF structure. For example, when thermal energy is applied to a non-directional material (i.e., no clear heating direction) during the drying process, or when the heating direction is substantially aligned with the gravity direction (i.e., with an offset angle between them of less than 90°) throughout the majority of the drying process, the resulting flexible porous dissolvable solid sheet tends to have a top surface with smaller pore openings and greater pore size variation in different regions along a direction through its thickness. In contrast, when the heating direction is offset from the gravity direction (i.e., with an offset angle between them of 90° or more) throughout the majority of the drying process, the resulting solid sheet may have a top surface with larger pore openings and reduced pore size variation in different regions along a direction through the thickness of such sheet. Correspondingly, the latter sheet is more receptive to water flowing therethrough, and therefore more soluble, than the former sheet. Without being bound by any theory, it is believed that the alignment or misalignment between the heating direction and the gravity direction during the drying process, and its duration, can significantly affect the interstitial liquid evacuation between the gas bubbles, which in turn can affect the pore expansion and pore opening in the solidified premix, resulting in solid sheets with very different OCF structures.
[0149] Thus, an important feature of the present disclosure is the use of an anti-gravity heating direction during the drying process, either throughout the entire drying time or at least for more than half of the drying time. Without being bound by any theory, it is believed that such an anti-gravity heating direction can reduce or prevent excessive interstitial liquid drainage toward the bottom region of the formed sheet during the drying process. Furthermore, since the top surface dries last, it allows more time for bubbles near the top surface of the formed sheet to expand and form pore openings on the top surface (because once the wet matrix is dried, the bubbles can no longer expand or form surface openings). As a result, the solid sheet formed by drying with such anti-gravity heating is characterized by an improved OCF structure, which allows for faster dissolution and other surprising and unexpected benefits.
[0150] In certain embodiments, the anti-gravity heating direction is provided by a conduction heating / drying configuration. For example, the aerated wet premix can be cast into a mold to form a sheet with two opposing faces. The mold can then be placed on a hot plate or heated moving belt or any other suitable heating device having a planar heated surface characterized by a controlled surface temperature of about 80°C to about 170°C, preferably about 90°C to about 150°C, more preferably about 100°C to about 140°C. By transferring heat energy by conduction from the planar heated surface to the bottom surface of the sheet of aerated wet premix, the solidification of the sheet starts from the bottom region and gradually moves upward to finally reach the top region. To ensure that the heating direction is primarily anti-gravity (i.e., substantially offset from the gravity direction) during this process, the heated surface is preferably the primary heat source of the sheet being dried. If any other heating source is present, the overall heating direction may be changed accordingly. More preferably, the heated surface is the only heat source of the sheet being dried.
[0151] In another particular embodiment, the anti-gravity heating direction is provided by a rotating drum heating / drying configuration, also referred to as drum drying or roller drying. Drum drying is a type of contact drying method used to dry liquid from a viscous premix of raw materials on the exterior surface of a heated rotatable drum (also referred to as a roller or cylinder) at relatively low temperatures to form a sheet-like article. It is a continuous drying process that is particularly suitable for drying large quantities. Because drying is performed at relatively low temperatures via contact heating / drying, it is typically energy efficient and does not adversely affect the compositional integrity of the raw materials.
[0152] The heated rotatable cylinder used in drum drying is internally heated, for example by steam or electricity, and rotated by an electric drive attached to a base bracket at a predetermined rotational speed. The heated rotatable cylinder or drum preferably has an outer diameter in the range of about 0.5 meters to about 10 meters, preferably about 1 meter to about 5 meters, more preferably about 1.5 meters to about 2 meters. It may have a controlled surface temperature of about 80°C to about 170°C, preferably about 90°C to about 150°C, more preferably about 100°C to about 140°C. Furthermore, such a heated rotatable cylinder rotates at a speed of about 0.005 rpm to about 0.25 rpm, preferably about 0.05 rpm to about 0.2 rpm, more preferably about 0.1 rpm to about 0.18 rpm.
[0153] The heated rotatable cylinder is preferably coated with a non-stick coating on its outer surface. The non-stick coating may be layered on the outer surface of the heated rotatable drum or may be secured to a medium on the outer surface of the heated rotatable drum. The medium may include, but is not limited to, heat-resistant non-woven fabric, heat-resistant carbon fiber, heat-resistant metal or non-metal mesh, etc. The non-stick coating can effectively maintain the structural integrity of the sheet-like article from damage during the sheet-forming process.
[0154] Also, a feeding mechanism is provided on the base bracket for adding an aerated wet premix of raw materials as described above onto the heated rotatable drum, thereby forming a thin layer of viscous premix on the outer surface of the heated rotatable drum. Thus, such a thin layer of premix is dried by the heated rotatable drum via contact heating / drying. The feeding mechanism includes a feeding trough installed on the base bracket, while the feeding trough is installed thereon at least one (preferably two) feeding hoppers, an imaging device for dynamic observation of feeding, and an adjusting device for adjusting the position and tilt angle of the feeding hopper. The adjusting device can be used to meet the need for different thicknesses of the formed sheet-like article by adjusting the distance between the feeding hopper and the outer surface of the heated rotatable drum. The adjusting device can also be used to adjust the feeding hopper to different tilt angles to meet the material requirements of speed and quality. The feeding trough may also include a rotating bar for stirring the wet premix therein to avoid phase separation and sedimentation before the wet premix is coated on the outer surface of the heated rotatable drum. Such rotating bars can also be used to aerate the wet premix if desired, as described above.
[0155] There may also be a heat shield attached to the base bracket to prevent rapid heat loss. The heat shield can also effectively save the energy required by the heated rotatable drum, thereby realizing a reduction in energy consumption and providing cost savings. The heat shield is a modular assembly structure or an integrated structure, and can be freely detached from the base bracket. The heat shield for sucking hot steam is provided with a suction device to avoid any water condensate from falling onto the sheet-like article being formed.
[0156] There may be an optional static scraping mechanism attached to the base bracket for scraping or scooping the sheet-like article already formed by the heated rotatable drum. The static scraping mechanism can be located on the base bracket or on one side thereof to transport the already formed sheet-like article downstream for further processing. The static scraping mechanism can be moved automatically or manually towards and away from the heated rotatable drum.
[0157] The method for making a flexible porous dissolvable solid sheet of the present disclosure is as follows: First, a heated rotatable drum having a non-stick coating on a base bracket is driven by an electric drive device. Then, an adjustment device adjusts a feeding mechanism so that the distance between the feeding hopper and the outer surface of the heated rotatable drum is a preset value. Meanwhile, the feeding hopper adds an aerated wet premix containing all or some of the raw materials for making a flexible porous dissolvable solid sheet onto the outer surface of the heated rotatable drum to form a thin layer of the aerated wet premix having a desired thickness thereon as described above in the previous section. Optionally, a suction device of the heat shield sucks the hot steam generated by the heated rotatable drum. Then, a static scraping mechanism scrapes / scoops up the dried / solidified sheet formed by the thin layer of the aerated wet premix after being dried at a relatively low temperature (e.g., 130° C.) by the heated rotatable drum. The dried / solidified sheet can also be peeled off manually or automatically without such a static scraping mechanism and then rolled up by a roller bar.
[0158] The total drying time in the present disclosure depends on the amount of compound and solids content in the wet premix, the drying temperature, the heat energy flow rate, and the thickness of the sheet material being dried. Preferably, the drying time is from about 1 minute to about 60 minutes, preferably from about 2 minutes to about 30 minutes, more preferably from about 2 minutes to about 15 minutes, even more preferably from about 2 minutes to about 10 minutes, and most preferably from about 2 minutes to about 5 minutes.
[0159] During such drying time, the heating direction is arranged to be substantially opposite the direction of gravity for more than half of the drying time, preferably more than 55% or 60% of the drying time (e.g., as in the rotary drum heating / drying configuration described above), more preferably more than 75% or even 100% of the drying time (e.g., as in the bottom conduction heating / drying configuration described above). Furthermore, the sheet of aerated wet premix can be dried for a first duration under a first heating direction and then dried for a second duration under a second, opposing heating direction, the first heating direction being substantially opposite the direction of gravity, the first duration being anywhere between 51% and 99% (e.g., 55%, 60%, 65%, 70% to 80%, 85%, 90%, or 95%) of the total drying time. Such a change in heating direction can be easily achieved by various other configurations not shown herein, for example, by a serpentine-shaped elongated heating belt that can rotate along its longitudinal center axis.
[0160] IV. Physical Properties of Solid Sheets The flexible porous dissolvable solid sheets formed by the above-described processing steps are characterized by an improved pore structure that allows easier water ingress into the sheet and faster dissolution of the sheet in water. Such improved pore structure is achieved primarily by adjusting the various processing conditions as described above, which are relatively independent or unaffected by the chemical formulation or specific ingredients used in making such sheets.
[0161] In general, such solid sheets may be characterized by (i) a percent open cell content of about 80%-100%, preferably about 85%-99%, more preferably about 90%-98%, as measured by Test 3 below, and (ii) an overall average pore size of about 100 μm to about 2000 μm, preferably about 150 μm to about 1000 μm, more preferably about 200 μm to about 600 μm, as measured by the Micro-CT method described in Test 2 below. The overall average pore size defines the porosity of the OCF structure of the present disclosure. The percent open cell content defines the interconnectivity between the pores in the OCF structure of the present disclosure. The interconnectivity of the OCF structure may also be described by the star volume or Structure Model Index (SMI) as disclosed in WO 2010 / 077627 and WO 2012 / 138820.
[0162] Such solid sheets of the present disclosure have opposing top and bottom surfaces, the top surface of which may be characterized by a surface average pore size, as measured by the SEM method described in Test 1 below, of greater than about 100 μm, preferably greater than about 110 μm, preferably greater than about 120 μm, more preferably greater than about 130 μm, and most preferably greater than about 150 μm.
[0163] Furthermore, the solid sheet formed by the improved heating / drying (e.g., rotary drum heating / drying) configuration of the present disclosure is characterized by a more uniform pore size distribution between different regions along its thickness direction compared to sheets formed by other heating / drying configurations (e.g., impingement oven). Specifically, the solid sheet of the present disclosure includes a top region adjacent to the top surface, a bottom region adjacent to the bottom surface, and a middle region therebetween, the top region, middle region, and bottom region all having the same thickness. Each of the top region, middle region, and bottom region of such a solid sheet is characterized by an average pore size, with the ratio of the average pore size in the bottom region to the average pore size in the top region (i.e., bottom to top average pore size ratio) being about 0.6 to about 1.5, preferably about 0.7 to about 1.4, preferably about 0.8 to about 1.3, more preferably about 1 to about 1.2. In comparison, solid sheets formed by impingement oven heating / drying configurations may have bottom to top average pore size ratios of greater than 1.5, typically about 1.7 to 2.2 (as shown in Example 1 below). Solid sheets of the present disclosure may also be characterized by bottom to middle average pore size ratios of about 0.5 to about 1.5, preferably about 0.6 to about 1.3, more preferably about 0.8 to about 1.2, and most preferably about 0.9 to about 1.1, as well as middle to top average pore size ratios of about 1 to about 1.5, preferably about 1 to about 1.4, and more preferably about 1 to about 1.2.
[0164] Furthermore, the relative standard deviation (RSTD) between the average pore sizes in the top, middle, and bottom regions of the solid sheets of the present disclosure is 20% or less, preferably 15% or less, more preferably 10% or less, and most preferably 5% or less. In contrast, solid sheets formed by impingement oven heating / drying configurations may have a relative standard deviation (RSTD) between the top / middle / bottom average pore sizes of more than 20%, perhaps more than 25%, or even more than 35%.
[0165] Preferably, the solid sheets of the present disclosure are further characterized by an average cell wall thickness of from about 5 μm to about 200 μm, preferably from about 10 μm to about 100 μm, and more preferably from about 10 μm to about 80 μm, as measured by Test 2 below.
[0166] The solid sheet of the present disclosure may contain a small amount of water. Preferably, it is characterized by a final moisture content of 0.5% to 25%, preferably 1% to 20%, more preferably 3% to 10%, based on the weight of the solid sheet, as measured by Test 4 below. A suitable final moisture content in the resulting solid sheet can ensure the desired flexibility / deformability of the sheet as well as provide a soft / smooth feel to the consumer. If the final moisture content is too low, the sheet may be too brittle or too stiff. If the final moisture content is too high, the sheet may be too sticky and its overall structural integrity may be compromised.
[0167] The solid sheets of the present disclosure may have a thickness ranging from about 0.6 mm to about 3.5 mm, preferably from about 0.7 mm to about 3 mm, more preferably from about 0.8 mm to about 2 mm, and most preferably from about 1 mm to about 2 mm. The thickness of the solid sheet can be measured using Test 5 described below. The solid sheet after drying may be slightly thicker than a sheet of aerated wet premix due to pore expansion resulting in an overall volume expansion.
[0168] A solid sheet of the present disclosure has a hardness of about 50 grams / m2, as measured by Test 6 described below. 2 ~ approx. 500g / m 2 , preferably about 150 g / m 2 ~ approx. 450g / m 2 , more preferably about 250 grams / m 2 ~ approx. 400g / m 2 The sheet may be further characterized by its basis weight.
[0169] Furthermore, the solid sheets of the present disclosure have a compressibility of about 0.05 grams / cm as measured by Test 7 below. 3 ~ approx. 0.5g / cm3 , preferably about 0.06 g / cm 3 ~ approx. 0.4g / cm 3 , more preferably about 0.07 grams / cm 3 ~ approx. 0.2g / cm 3 , and most preferably about 0.08 grams / cm 3 ~ approx. 0.15g / cm 3 The density of the solid sheets of the present disclosure may be lower than that of a sheet of aerated wet premix due in part to pore expansion resulting in an overall volume expansion. In some embodiments, the solid sheets of the present disclosure may have a density of about 0.06 grams / cm. 3 ~ approx. 0.16g / cm 3 , preferably about 0.07 g / cm 3 ~ approx. 0.15g / cm 3 , more preferably about 0.08 grams / cm 3 ~ approx. 0.145 g / cm 3 Solid articles containing such relatively low density sheets may achieve even more improved leakage performance.
[0170] Additionally, the solid sheets of the present disclosure have a thickness of about 0.03 m, as measured by Test 8 described below. 2 / g~approx.0.25m 2 / g, preferably about 0.04m 2 / g~approx.0.22m 2 / g, more preferably 0.05m 2 / g~0.2m 2 / g, most preferably 0.1m 2 / g~0.18m 2 The specific surface area of the solid sheet of the present disclosure can indicate its porosity and can affect its dissolution rate, e.g., the higher the specific surface area, the more porous the sheet is and the faster its dissolution rate.
[0171] In a preferred embodiment, the solid sheet according to the present disclosure and / or the dissolvable solid article according to the present disclosure comprises: an open cell percentage of 85% to 99%, preferably 90% to 98%, and / or an overall average pore size of 150 μm to 1000 μm, preferably 200 μm to 600 μm, and / or an average cell wall thickness of 5 μm to 200 μm, preferably 10 μm to 100 μm, more preferably 10 μm to 80 μm, and / or a final moisture content of 0.5% to 25%, preferably 1% to 20%, more preferably 3% to 10%, based on the weight of the solid sheet article; and / or a thickness of 0.6 mm to 3.5 mm, preferably 0.7 mm to 3 mm, more preferably 0.8 mm to 2 mm, and most preferably 1 mm to 2 mm; and / or Approximately 50g / m 2 ~ approx. 500g / m 2 , preferably about 150 g / m 2 ~ approx. 450g / m 2 , more preferably about 250 grams / m 2 ~ approx. 400g / m 2 and / or 0.05g / cm 3 ~0.5g / cm 3 , preferably 0.06 g / cm 3 ~0.4g / cm 3 , more preferably 0.07 g / cm 3 ~0.2g / cm 3 , most preferably 0.08 g / cm 3 ~0.15g / cm 3 and / or 0.03m 2 / g~0.25m 2 / g, preferably 0.04m 2 / g~0.22m 2 / g, more preferably 0.05m 2 / g~0.2m 2 / g, most preferably 0.1m 2 / g~0.18m 2 It is characterized by its specific surface area in g / g.
[0172] V: Conversion rate Once the flexible dissolvable porous solid sheet articles of the present disclosure have been formed, two or more of such sheets can be further combined and / or processed as described above to form dissolvable solid articles of any desired three-dimensional shape, including, but not limited to, spheres, cubes, rectangles, ovals, cylinders, rods, sheets, flowers, sectors, stars, disks, etc. The sheets may be combined and / or processed by any means known in the art, including, but not limited to, chemical means, mechanical means, and combinations thereof. Such combining and / or processing steps are collectively referred to herein as a "conversion" process, i.e., which serves to convert two or more flexible dissolvable porous sheets of the present disclosure into a dissolvable solid article having a desired three-dimensional shape.
[0173] Further, the multi-layered dissolvable solid articles of the present disclosure may be characterized by a maximum dimension D and a minimum dimension z (perpendicular to the maximum dimension), with the D / z ratio (hereinafter also referred to as the "aspect ratio") ranging from 1 to about 10, preferably from about 1.4 to about 9, preferably from about 1.5 to about 8, more preferably from about 2 to about 7. It is noted that when the aspect ratio is 1, the dissolvable solid article has a spherical shape. When the aspect ratio is about 1.4, the dissolvable solid article has a cubic shape. The multi-layered dissolvable solid articles of the present disclosure may have a minimum dimension z greater than about 3 mm but less than about 20 cm, preferably from about 4 mm to about 10 cm, more preferably from about 5 mm to about 30 mm.
[0174] The multi-layered dissolvable solid article described above may include two or more such flexible dissolvable porous sheets. For example, it may include about 4 to about 50, preferably about 5 to about 40, and more preferably about 6 to about 30 flexible dissolvable porous sheets. The improved OCF structure in the flexible dissolvable porous sheets made according to the present disclosure allows many sheets (e.g., 15 to 40) to be stacked together while still providing a sufficient overall dissolution rate for the stack.
[0175] In a particularly preferred embodiment of the present disclosure, the multi-layer dissolvable solid article comprises 15-40 layers of the flexible dissolvable porous sheet described above and has an aspect ratio in the range of about 2 to about 7.
[0176] The multi-layered dissolvable solid articles of the present disclosure may include individual sheets of different colors that are visible from the exterior (e.g., one or more sides) of such articles. Such visible sheets of different colors are aesthetically pleasing to consumers. Furthermore, the different colors of the individual sheets can provide visual cues indicative of different benefit agents contained in the individual sheets. For example, the multi-layered dissolvable solid article may include a first sheet having a first color and containing a first benefit agent, and a second sheet having a second color and containing a second benefit agent, where the first color provides a visual cue indicative of the first benefit agent and the second color provides a visual cue indicative of the second benefit agent.
[0177] Also, one or more functional ingredients can be "sandwiched" between the individual sheets of the multi-layered dissolvable solid article as described above, for example, by spraying, sprinkling, dusting, coating, spreading, dipping, pouring, or even vapor deposition. To avoid interference of such functional ingredients with the cut seal or edge seal near the periphery of the individual sheets, such functional ingredients are preferably located within the central region between two adjacent sheets, the central region being defined as an area spaced apart by a distance of at least 10% of the maximum dimension D. Suitable functional ingredients can be selected from the group consisting of cleaning actives (surfactants, free perfumes, encapsulated perfumes, perfume microcapsules, silicones, emollients, enzymes, bleaches, colorants, builders, rheology modifiers, pH adjusters, and combinations thereof) and personal care actives (e.g., emollients, moisturizers, conditioning agents, and combinations thereof).
[0178] In a particularly preferred embodiment of the present disclosure, the coating composition is applied to the surface of at least one of the two or more flexible dissolvable porous sheets described above, and then the two or more sheets are stacked together to form a three-dimensional multi-layer shape. The coating composition can be applied between the individual sheets of the multi-layer dissolvable solid article by any suitable means, such as spraying, sprinkling, dusting, coating, spreading, dipping, pouring, rolling, or even vapor deposition. The coating composition can include surfactants, fragrances, solvents (e.g., glycerol, diethylene glycol, dipropylene glycol, ethanol, water, etc.), rheology modifiers (e.g., cellulose; guar; polyethylene oxide, polypropylene oxide, and POE-PPO copolymers; polyvinylpyrrolidone, cross-linked polyvinylpyrrolidone; polyvinyl alcohol; polyethyleneimine; silicon dioxide; water-swellable clays; gums, and derivatives thereof), and / or other formulation ingredients. The solid coating composition can be applied to the surface of at least one of the two or more flexible dissolvable porous sheets described above at 20°C and 1s. -1 The coating composition is characterized by a viscosity of about 1 cps to about 25,000 cps, preferably about 2 cps to about 10,000 cps, more preferably about 3 cps to about 5,000 cps, and most preferably about 1,000 cps to about 5,000 cps, as measured by . The viscosity of the coating composition can be measured using a Malvern Kinexus Lab+ rheometer (CP1 / 50 SR3468 SS) with a cone and plate geometry at a gap width of 0.054 mm, a temperature of 20° C., and a shear rate of 1.0 reciprocal seconds over 360 seconds.
[0179] Preferably, two or more sheets are stacked together such that the coating composition is not present on any of the outer surfaces of the stack.A surprising and unexpected discovery of the present disclosure is that three-dimensional multi-layer solid articles containing a coating composition have significantly improved dissolution profiles over multi-layer solid articles having the same total amount of surfactant but not including the coating composition.
[0180] Test Method Test 1: Scanning Electron Microscopic (SEM) Method for Determining Surface Average Pore Size of Sheet Articles SEM micrographs of the samples are obtained using a Hitachi TM3000 Tabletop Microscope (S / N: 123104-04). Samples of the solid sheet articles of the present disclosure are approximately 1 cm x 1 cm in area and are cut from larger sheets. Images are collected at 50X magnification and the unit is operated at 15 kV. A minimum of five microscopic images are collected from randomly selected locations across each sample, resulting in an estimated average pore size of approximately 43.0 mm. 2 Obtain the total analyzed area.
[0181] The SEM micrographs are then first processed using an image analysis toolbox in Matlab®. Images are converted to grayscale if necessary. For a given image, a histogram of intensity values for every single pixel is generated using the Matlab® “imhist” function. Typically, such a histogram reveals two separate distributions, corresponding to the lighter sheet surface pixels and the darker area pixels within the pores. A threshold is selected that corresponds to an intensity value between the peak values of these two distributions. All pixels with intensity values lower than this threshold are then set to an intensity value of 0, and pixels with intensity values higher than it are set to 1, thereby generating a binary black and white image. The binary image is then analyzed using ImageJ (https: / / imagej.nih.gov, version 1.52a) to examine both the pore area ratio and the pore size distribution. The scale bar of each image is used to provide a pixel / mm scaling factor. For analysis, the autothresholding and analyze particles functions are used to isolate each pore. Output from the analysis function includes area ratios for the whole image and pore area, and pore perimeter for each detected pore.
[0182] The average pore size is D A 50, i.e., 50% of the total pore area is D A It is composed of pores having a hydraulic diameter of 50 or less average diameter.
[0183] Hydraulic diameter='4 * Pore area (m 2 ) / pore circumference (m)'.
[0184] This is an equivalent diameter calculated to take into account pores that are not all circular.
[0185] Test 2: Micro-Computed Tomographic (μCT) Methods for Determining the Average Pore Size and Average Cell Wall Thickness of Whole or Regions of Open Cell Foam (OCF) Porosity is the ratio of void space to the total space occupied by the OCF. Porosity can be calculated from a μCT scan by segmenting the void space by thresholding and determining the ratio of void voxels to total voxels. Similarly, solid volume fraction (SVF) is the ratio of solid space to total space, and SVF can be calculated as the ratio of occupied voxels to total voxels. Both porosity and SVF are average scalar values that do not provide structural information such as the pore size distribution across the height of the OCF or the average cell wall thickness of the OCF struts.
[0186] To characterize the 3D structure of the OCF, the sample is imaged using a μCT X-ray scanning device capable of acquiring a data set with high isotropic spatial resolution. An example of a suitable instrument is a SCANCO System model 50 μCT scanner (Scanco Medical AG, Bruttisellen, Switzerland) operating with the following settings: energy level: 45 kVp at 133 μA, projections: 3000, field of view: 15 mm, integration time: 750 ms, averages: 5, and voxel size: 3 μm per pixel. After the scan and subsequent data reconstruction are completed, the scanner system creates a 16-bit data set, referred to as an ISQ file, in which the gray levels reflect the changes in X-ray attenuation and thus relate to the material density. The ISQ file is then converted to 8-bit using a scaling factor.
[0187] Scanned OCF samples are typically prepared by punching a core approximately 14 mm in diameter. The OCF punch is placed flat on a low damping foam and then mounted into a 15 mm diameter plastic cylindrical tube for scanning. A scan of the sample is acquired such that the entire volume of all mounted cut samples is included in the data set. From this larger data set, smaller sub-volumes of the sample data set are extracted from the total cross-section of the scanned OCF to create a 3D data slab, where the pores can be qualitatively evaluated without edge / boundary effects.
[0188] To characterize the pore size distribution in the height direction, a strut size, local thickness map algorithm, or LTM, is implemented on the subvolume dataset. The LTM method starts with Euclidean Distance Mapping (EDM), assigning each void voxel a gray level value equal to its distance from its nearest boundary. Based on the EDM data, the 3D void space representing the pores (or the 3D solid space representing the struts) is tessellated with spheres sized to match the EDM values. Voxels enclosed by the spheres are assigned the radial value of the largest sphere. In other words, each void voxel (or solid voxel of a strut) is assigned the radial value of the largest sphere that both fits within the void space boundary (or solid space boundary of a strut) and contains the assigned voxel.
[0189] The 3D labeled sphere distribution output from the LTM data scan is processed as a stack of two-dimensional images in the height direction (or Z direction) and can be used to estimate the change in sphere diameter from slice to slice as a function of OCF depth. Strut thickness is processed as a 3D data set and average values can be evaluated for all or part of the subvolume. Calculations and measurements were performed using Thermo Fisher Scientific's AVIZO Lite (9.2.0) and Mathworks' MATLAB (R2017a).
[0190] Test 3: Percentage of Open Cells in Sheet Articles The percent open cell content is measured through gas pycnometry. Gas pycnometry is a common analytical technique that uses gas displacement to accurately measure volume. An inert gas such as helium or nitrogen is used as the displacement medium. A sample of the solid sheet article of the present disclosure is sealed in an instrument compartment of known volume, charged with the appropriate inert gas, and then expanded to another precise internal volume. The pressure before and after expansion is measured and used to calculate the volume of the sample article.
[0191] ASTM Standard Test Method D2856 provides a procedure for determining the percentage of open cells using an older model of an air comparison pycnometer. This device is no longer manufactured. However, one can conveniently and precisely determine the percentage open cells by performing tests using a Micromeritics AccuPyc pycnometer. ASTM Procedure D2856 describes five methods (A, B, C, D, and E) for determining the percentage of open cells in foamed materials. For these experiments, samples can be analyzed using an Accupyc 1340 with ASTM foampyc software using nitrogen gas. ASTM Procedure Method C should be used to calculate the percentage open cells. This method simply compares the geometric volume determined using calipers and standard volume calculations to the open cell volume measured by the Accupyc according to the following equation: Percent open cell = open cell volume of sample / geometric volume of sample * 100
[0192] It is recommended that these measurements be performed by Micromeretics Analytical Services, Inc., One Micromeritics Dr, Suite 200, Norcross, GA 30093. More information on this technique is available on the Micromeretics Analytical Services website (www.particletesting.com or www.micromeritics.com) or published in "Analytical Methods in Fine Particle Technology" by Clyde Orr and Paul Webb.
[0193] Test 4: Final Moisture Content of Sheet Articles The final moisture content of the solid sheet article of the present disclosure is obtained by using a Mettler Toledo HX204 Moisture Analyzer (S / N B706673091). A minimum of 1 g of the dried sheet article is placed on the measurement tray. A standard program is then run with additional program settings of 10 minutes analysis time and 110°C temperature.
[0194] Test 5: Thickness of Sheet Article The thickness of the flexible porous solid sheet articles of the present disclosure is obtained using a micrometer or feeler gauge, such as a Mitutoyo Corporation Digital Disk Stand Micrometer Model Number IDS-1012E (Mitutoyo Corporation, 965 Corporate Blvd, Aurora, IL, USA 60504), which has a platen with a diameter of 1 inch, weighs about 32 grams, and has a pressure of about 0.09 psi (6.32 gm / cm 2 ) the thickness is measured at an applied pressure of 1000 psi.
[0195] The thickness of a flexible porous dissolvable solid sheet article is measured by raising the platen, placing a portion of the sheet article on a stand directly beneath the platen, carefully lowering the platen to touch the sheet article, releasing the platen, and measuring the thickness of the sheet article in millimeters on a numeric display. Except for uneven, stiffer substrates, the sheet article should be fully extended over all edges of the platen to ensure that the thickness is measured at the least possible surface pressure.
[0196] Test 6: Basis Weight of Sheet Articles The basis weight of the flexible porous dissolvable solid sheet article of the present disclosure is determined by the weight of the sheet article per its area (grams / m 2 The area is calculated as the projected area on a flat surface perpendicular to the outer edges of the sheet article. The solid sheet articles of the present disclosure are cut into 10 cm x 10 cm square samples so that their areas are known. Each such square sample is then weighed and the resulting weight is then multiplied by 100 cm. 2 Divide by the known area to determine the corresponding basis weight.
[0197] For irregularly shaped articles, if it is a flat object, the area is calculated based on the area enclosed within the perimeter of such object. Thus, for a spherical object, the area is calculated based on the average diameter, 3.14 x (diameter / 2) 2 The area is calculated as: diameter x length. Thus, for cylindrical objects, the area is calculated based on the average diameter and average length. For irregularly shaped three-dimensional objects, the area is calculated based on the side with the largest outer dimension projected onto a flat surface oriented perpendicular to this side. This can be accomplished by carefully tracing the outer dimensions of the object with a pencil on a piece of graph paper and then calculating the area by approximately counting the squares and multiplying by the known area of the square, or by taking a photograph of the traced area (shaded for contrast) including a scale and using image analysis techniques.
[0198] Test 7: Density of Sheet Articles The density of the flexible porous dissolvable solid sheet articles of the present disclosure is determined by the following equation: Calculated density = basis weight of porous solid / (thickness of porous solid x 1,000). The basis weight and thickness of the flexible porous solid are determined according to the methodology described herein.
[0199] Test 8: Specific surface area of sheet article The specific surface area of flexible porous soluble solid sheet articles is measured via a gas adsorption technique. Surface area is a measurement of the exposed surface of a solid sample on a molecular scale. BET (Brunauer, Emmet, and Teller) theory is the most well-known model used to determine surface area and is based on gas adsorption isotherms. Gas adsorption uses physical adsorption and capillary condensation to measure gas adsorption isotherms. This technique is summarized by the following steps: The sample is placed in a sample tube and heated under vacuum or gas flow to remove contaminants on the surface of the sample. The sample weight is obtained by subtracting the empty sample tube weight from the combined weight of the degassed sample and sample tube. The sample tube is then placed on the analysis port and the analysis begins. The first step in this analysis process is to evacuate the sample tube and then measure the free space volume in the sample tube using helium gas at liquid nitrogen temperature. The sample is then evacuated again and the helium gas is removed. The instrument then begins to collect the adsorption isotherm by dosing krypton gas at user-specified intervals until the required pressure measurement is achieved. The samples may then be analyzed using an ASAP2420 with krypton gas adsorption. It is recommended that these measurements be performed by Micromeretics Analytical Services, Inc., One Micromeritics Dr, Suite 200, Norcross, GA 30093. More information on this technique is available on the Micromeretics Analytical Services website (www.particletesting.com or www.micromeritics.com) or published in the book "Analytical Methods in Fine particle Technology" by Clyde Orr and Paul Webb.
[0200] Test 9: Hand dissolution method One sample article having dimensions of approximately 30 mm x 30 mm x 3-5 mm is placed on the palm of the tester wearing a nitrile glove. 3of tap water is rapidly applied to the sample article by syringe. In a circular motion, the palms of the tester's hands are rubbed together two strokes at a time (maximum 30 strokes) until dissolution occurs. The hand dissolution rate is reported as the number of strokes it takes for the sample article to completely dissolve (up to a maximum of 30 strokes). The more strokes, the slower the hand dissolution rate. The fewer strokes, the faster the hand dissolution rate.
[0201] Test 10: Long-Lasting Freshness Test A basin is filled with 13 liters of reverse osmosis ("RO") water at a temperature of about 28°C. The sample article is immersed in such water for 5 seconds and allowed to dissolve to form a cleaning solution. The cleaning solution is agitated by hand for 30 seconds to ensure complete dissolution of the sample article. A test cloth (containing 0.2 kg of hand towels) is placed in the cleaning solution and allowed to soak for 5 minutes. The test cloth is then removed from the cleaning solution and squeezed by hand to remove excess water. The test cloth is then hung up to dry overnight. The dried cloth is subjected to an odor test by a sensory panel of 4 trained panelists. Each panelist sniffs the dried cloth before and after rubbing, thereby providing his / her assessment. The individual assessments are then averaged to provide an overall long-term freshness retention score. EXAMPLES
[0202] Example 1: Comparative dissolution profiles of solid sheet articles containing directly added PMC and solid sheet articles containing post-added PMC 1) Preparation of Solid Sheet Articles with Directly Added PMC A flexible, porous, dissolvable solid sheet article containing directly added PMC is prepared as follows.
[0203] First, a wet premix is prepared containing 2.44% PMC slurry (containing 32.25% PMC and 67.75% water), 9.61% PVA, 9.86% DEEDMAC, 13.44% glycerin, 1.29% starch, and the balance water for a total solids content of about 35% by weight (i.e., the total water content in the slurry is about 65% by weight). Specifically, PVA is a polyvinyl alcohol having a hydrolysis level of 88% and a degree of polymerization of about 1700, and is commercially available from Sigma Aldrich. DEEDMAC is commercially available from Evonik Industries under the trade name Rewoquat. The PMC slurry can include a first type of PMC having a shell of melamine crosslinked with formaldehyde and a cationic coating of polyvinylformamide formed thereon ("HEPMC"), which is commercially available from Encapsys (Appleton, WI). Alternatively, the PMC slurry can contain a second type of PMC having an uncoated polyacrylate shell ("PAC PMC"), also available commercially from Encapsys (Appleton, Wis.).
[0204] The method for preparing the wet premix is as follows. 1. First, add the water and glycerin together to a glass beaker and stir at 200 rpm using an overhead stirrer. 2. With continued stirring, the PVA is then slowly added to the beaker containing the water and glycerin, without causing the solution to foam or the PVA to clump. 3. The beaker is then placed in a water bath and heated with continued stirring to 80° C. The beaker is covered with cling film or tin foil to reduce water evaporation and mixing is allowed to continue for at least 1.0 hour. 4. The remaining ingredients (e.g., PMC slurry, DEEDMAC, starch, etc.) are weighed and added together in a separate glass beaker. The remainder of the water needed to achieve a total water content of 65% in the slurry is also added to this beaker. 5. Place the beaker in an 80° C. water bath and stir the contents with an overhead stirrer at 500 rpm for at least 30 minutes. 6. Once the predefined mixing time has been reached in both beakers, add both contents together into a single glass beaker followed by continuous stirring at 500 rpm and maintaining the temperature at 80° C. for at least an additional 30 minutes.
[0205] The wet premix thus formed has a viscosity of about 19254.6 cps. It is then aerated as follows. 1. Preheat an Aeros A20 continuous aerator consisting of a jacketed hopper (Model JCABT10) and an A20 mixhead to 80° C. using a water bath and pump. 2. The previously prepared slurry is then added to the hopper. The aerator device is then turned on and the mix head speed, feed pump speed, and air flow rate are set to 600, 500, and 100 respectively. 3. The aerated slurry is collected from the aerator outlet and its density is measured by filling a density cup of known volume and weighing the mass of the aerated slurry. With the above aerator settings, it is approximately 0.225 g / cm 3 An aerated slurry density of 0.1% is achieved.
[0206] Flexible and porous solid sheets with thicknesses of approximately 0.8-1.5 mm are produced using a rotary drum dryer process as follows. 1. Preheat a rotary drum dryer (having a drum diameter of about 1.5 m) to about 100°C. 2. The aerated slurry collected from the outlet of the Aeros A20 is fed into the feed trough of a drum dryer. 3. Once loaded, the drum dryer is started and the rotation speed is set to provide a residence time of the slurry on the heated drum of approximately 15 minutes. 4. Once dry, the flexible and porous sheet so formed is peeled off from the drum surface and placed in a plastic bag.
[0207] The solid sheets with directly added HEPMC or PAC PMC are then stored for 24 hours (i.e., the acclimation step) at an ambient relative humidity of 50±2% and a temperature of 23±1° C. The average thickness across Sheet 1 is 1.2107 mm with a standard deviation of 0.0464.
[0208] 2) Preparation of Solid Sheet Articles with Post-Added PMC A flexible, porous, dissolvable solid sheet article containing post-added PMC is prepared as follows.
[0209] Specifically, a wet premix is prepared containing 9.85% PVA, 10.1% DEEDMAC, 13.77% glycerin, 1.33% starch, and the balance water for a total solids content of about 35% by weight (i.e., the total water content in the slurry is about 65% by weight).
[0210] The method for preparing the wet premix is as follows. 1. First, add the water and glycerin together to a glass beaker and stir at 200 rpm using an overhead stirrer. 2. With continued stirring, the polyvinyl alcohol is then slowly added to the beaker containing the water and glycerin, without causing the solution to foam or the polyvinyl alcohol to clump. 3. The beaker is then placed in a water bath and heated with continued stirring to 80° C. The beaker is covered with cling film or tin foil to reduce water evaporation and mixing is allowed to continue for at least 1.0 hour. 4. The remaining ingredients (e.g., DEEDMAC, starch, etc.) are weighed and added together in a separate glass beaker. The remainder of the water needed to achieve a total water content of 65% in the slurry is also added to this beaker. 5. Place the beaker in an 80° C. water bath and stir the contents with an overhead stirrer at 500 rpm for at least 30 minutes. 6. Once the predefined mixing time has been reached in both beakers, add both contents together into a single glass beaker followed by continuous stirring at 500 rpm and maintaining the temperature at 80° C. for at least an additional 30 minutes.
[0211] The wet premix thus formed has a viscosity of about 19254.6 cps. It is then aerated as follows. 4. Preheat an Aeros A20 continuous aerator consisting of a jacketed hopper (Model JCABT10) and an A20 mixhead to 80° C. using a water bath and pump. 5. The previously prepared slurry is then added to the hopper. The aerator device is then turned on and the mix head speed, feed pump speed, and air flow rate are set at 600, 500, and 100 respectively. 6. The aerated slurry is collected from the aerator outlet and its density is measured by filling a density cup of known volume and weighing the mass of the aerated slurry. With the above aerator settings, it is approximately 0.225 g / cm 3 An aerated slurry density of 0.1% is achieved.
[0212] Flexible and porous solid sheets with thicknesses of approximately 0.8-1.5 mm are produced using a rotary drum dryer process as follows. 5. Preheat a rotary drum dryer (having a drum diameter of about 1.5 m) to about 130°C. 6. The aerated slurry collected from the outlet of the Aeros A20 is fed into the feed trough of a drum dryer. 7. Once loaded, the drum dryer is started and the rotation speed is set to provide a residence time of the slurry on the heated drum of approximately 15 minutes. 8. Once dry, the flexible and porous sheet so formed is peeled off from the drum surface and placed in a plastic bag.
[0213] The solid sheets are then stored for 24 hours (i.e., the conditioning step) at 50±2% ambient relative humidity and a temperature of 23±1° C. The average thickness across Sheet 1 is 1.2107 mm with a standard deviation of 0.0464.
[0214] Subsequently, 0.352 grams of PMC slurry containing 32.25% HEPMC or PAC PMC and 67.75% water is applied between the solid sheets. The solid sheets with such post-added HEPMC or PAC PMC are then stored for another 24 hours under the same humidity and temperature conditions (50±2% and 23±1° C.).
[0215] Flexible porous dissolvable solid sheets made by the above method with either direct-added or post-added HEPMC or PAC PMC are then tested using the hand dissolution method described above in Test 9. The sheet formulations and their respective hand dissolution test results are shown below.
[0216] [Table 1]
[0217] The above data demonstrate that flexible, porous, dissolving solid sheets containing directly added PMC (either HEPMC or PAC PMC) have significantly improved dissolution profiles compared to similar solid sheets containing post-added PMC.
[0218] Example 2: Comparison of Long-Term Freshness Maintenance of Solid Sheet Articles Containing Directly Added PMC and Solid Sheet Articles Containing Post-Added PMC Flexible porous dissolving solid sheets containing either direct-added or post-added PAC PMC are made by the same process as in Example 1. Such solid sheets are then tested using the long-term freshness retention method described above in Test 10. The sheet formulations and their respective freshness retention test results are shown below.
[0219] [Table 2]
[0220] [Table 3] a Scores were assigned by each panelist as follows, with "0" meaning "Sheets C and 3 are the same," "1" meaning "Sheet C seems better than Sheet 3, but not sure," "2" meaning "Sheet C is slightly better than Sheet 3," and "3" meaning "Sheet C is significantly better than Sheet 3."
[0221] The above data shows that flexible porous dissolvable solid sheets containing lower loadings of direct-added PMC exhibit the same long-term freshness benefit as similar solid sheets containing higher loadings of post-added PMC when the test cloth is not rubbed, but exhibit even better long-term freshness benefit when the test cloth is rubbed. This result is surprising and unexpected, especially in opposition to conventional wisdom.
[0222] Example 4: Exemplary Solid Sheet Articles with Direct-Loaded Microcapsules Below are examples of flexible porous dissolvable solid sheet articles containing direct-added microcapsules made by process steps similar to those in Example 1. Some of the sheets may further contain a coating composition containing fragrance, non-ionic surfactant, and / or solvent (e.g., dipropylene glycol) on their surface.
[0223] [Table 4]
[0224] [Table 5]
[0225] [Table 6]
[0226] [Table 7]
[0227] Dimensions and values disclosed herein should not be understood as being strictly limited to the exact numerical values recited. Instead, unless otherwise indicated, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm."
[0228] All documents cited herein, including any cross-referenced or related patents or patent applications, and any patent applications or patents to which this application claims priority or benefit, are incorporated herein by reference in their entirety, unless expressly stated to the contrary. The citation of any document shall not be deemed to be prior art to any invention disclosed or claimed herein, or to teach, suggest or disclose such invention, either alone or in combination with any other reference(s). Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall govern.
[0229] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended to cover in the appended claims all such changes and modifications that are within the scope of this invention.
Claims
1. 1. A method for preparing a solid sheet article, comprising: a) providing a wet premix comprising a water soluble polymer, a surfactant, and microcapsules, said wet premix having a viscosity of from 1,000 cps to 25,000 cps measured at 40° C. and 1 s-1, each of said microcapsules comprising a core and a shell at least partially surrounding said core, said core comprising a benefit agent; b) aerating the wet premix to form an aerated wet premix having a density of 0.05 to 0.5 g / mL; c) forming the aerated wet premix into a sheet; d) drying the formed sheet at a temperature of from 70° C. to 200° C. for a drying time of from 1 minute to 60 minutes to form the solid sheet article; Including, said solid sheet article comprising 1% to 20% microcapsules based on the total weight of said solid sheet article; the surfactant in the wet premix is a cationic and / or nonionic surfactant selected from the group consisting of diester quaternary ammonium (DEQA) compounds, C12-C22 mono / di-alkyl quaternary ammonium compounds, C12-C22 mono-alkylamine compounds, C8-C18 alkyl ethoxylated alcohols having a weight average degree of ethoxylation of from about 1 to about 20, and combinations thereof, each of the microcapsules further comprising a cationic coating on its shell, the cationic coating being formed from a cationic polymer selected from the group consisting of polyvinylformamide, partially hydroxylated polyvinylformamide, polyvinylamine, polyethyleneimine, ethoxylated polyethyleneimine, cationically modified polysaccharides, and combinations thereof; or 10. A method according to claim 1, wherein the surfactant in the wet premix is an anionic and / or nonionic surfactant selected from the group consisting of C6-C20 linear alkyl benzene sulfonates (LAS), C6-C20 linear or branched alkyl alkoxy sulfates (AAS) having a weight average degree of alkoxylation ranging from 0.5 to 10, C6-C20 linear or branched alkyl sulfates (AS), C6-C20 linear or branched alkyl alkoxylated alcohols (AA) having a weight average degree of alkoxylation ranging from 5 to 15, and combinations thereof; and the shell of each of the microcapsules comprises an anionic polymer selected from the group consisting of poly(meth)acrylates, polyvinyl(meth)acrylates, poly(ethylene-maleic anhydride), and combinations thereof.
2. The benefit agent in the core of each of the microcapsules may be selected from the group consisting of fragrances, silicone oils, waxes, hydrocarbons, higher fatty acids, essential oils, lipids, skin cooling agents, vitamins, sunscreens, antioxidants, glycerin, catalysts, bleach particles, silicone dioxide particles, odor reducing agents, odor control materials, chelating agents, antistatic agents, fabric softeners, insect and moth repellents, colorants, thickeners, drape and foam conditioning agents, smoothing agents, wrinkle control agents, sanitizing agents, disinfectants, bacterial inhibitors, mold inhibitors, mildew inhibitors, antiviral agents, drying agents, stain resistant agents, soil release agents, fabric refreshing agents, wash and 2. The method of claim 1, wherein the benefit agent in the core of each of the microcapsules is selected from the group consisting of feel maintaining agents, chlorine bleach odor control agents, dye fixatives, dye transfer inhibitors, color retention agents, optical brighteners, color restoration / renewal agents, anti-fade agents, whiteness enhancers, anti-abrasion agents, abrasion resistance agents, fabric integration agents, anti-abrasion agents, foam suppressants, defoamers, UV protection agents, sun fade inhibitors, anti-allergy agents, enzymes, waterproofing agents, fabric comfort agents, shrink resistance agents, stretch resistance agents, stretch recovery agents, skin care agents, natural actives, antimicrobial actives, antiperspirant actives, cationic polymers, dyes, and combinations thereof, and preferably the benefit agent in the core of each of the microcapsules comprises a fragrance.
3. 1. A flexible porous dissolvable solid sheet article comprising a water soluble polymer, a surfactant, and a plurality of microcapsules, said solid sheet article having opposed first and second planar surfaces, each of said plurality of microcapsules comprising a core and a shell at least partially surrounding said core, said core comprising a benefit agent, at least one of said microcapsules being located between said opposed first and second planar surfaces, said solid sheet article being characterized by (i) an open cell content of 80% to 100%, and (ii) an overall average pore size of 100 μm to 2000 μm, said solid sheet article comprising 1% to 20% microcapsules based on a total weight of said solid sheet article; the surfactant is a cationic and / or nonionic surfactant selected from the group consisting of diester quaternary ammonium (DEQA) compounds, C12-C22 mono / di-alkyl quaternary ammonium compounds, C12-C22 mono-alkylamine compounds, C8-C18 alkyl ethoxylated alcohols having a weight average degree of ethoxylation of from about 1 to about 20, and combinations thereof, each of the microcapsules further comprising a cationic coating on its shell, the cationic coating being formed from a cationic polymer selected from the group consisting of polyvinylformamide, partially hydroxylated polyvinylformamide, polyvinylamine, polyethyleneimine, ethoxylated polyethyleneimine, cationically modified polysaccharides, and combinations thereof; or A flexible porous dissolvable solid sheet article, wherein the surfactant is an anionic and / or nonionic surfactant selected from the group consisting of C6-C20 linear alkyl benzene sulfonate (LAS), C6-C20 linear or branched alkyl alkoxy sulfate (AAS) having a weight average degree of alkoxylation ranging from 0.5 to 10, C6-C20 linear or branched alkyl sulfate (AS), C6-C20 linear or branched alkyl alkoxylated alcohol (AA) having a weight average degree of alkoxylation ranging from 5 to 15, and combinations thereof, and the shell of each of the microcapsules comprises an anionic polymer selected from the group consisting of poly(meth)acrylate, polyvinyl(meth)acrylate, poly(ethylene-maleic anhydride), and combinations thereof.
4. 4. The flexible porous dissolvable solid sheet article of claim 3, wherein a majority of said plurality of microcapsules are located between said opposing first and second planar surfaces of said solid sheet article.
5. The benefit agent in the core of each of the microcapsules may be selected from the group consisting of fragrances, silicone oils, waxes, hydrocarbons, higher fatty acids, essential oils, lipids, skin cooling agents, vitamins, sunscreens, antioxidants, glycerin, catalysts, bleach particles, silicone dioxide particles, odor reducing agents, odor control materials, chelating agents, antistatic agents, fabric softeners, insect and moth repellents, colorants, thickeners, drape and foam conditioning agents, smoothing agents, wrinkle control agents, sanitizing agents, disinfectants, bacterial inhibitors, mold inhibitors, mildew inhibitors, antiviral agents, drying agents, stain resistant agents, soil release agents, fabric refreshing agents, fresh wash maintaining agents, chlorine bleaching agents, and the like.
5. The flexible porous dissolvable solid sheet article of claim 3 or 4, wherein said benefit agents in the core of each of said microcapsules are selected from the group consisting of white odor control agents, dye fixatives, dye transfer inhibitors, color retention agents, optical brighteners, color restoration / renewal agents, anti-fade agents, whiteness enhancers, anti-abrasion agents, abrasion resistance agents, fabric integration agents, anti-abrasion agents, foam inhibitors, defoamers, UV protection agents, sun fade inhibitors, anti-allergy agents, enzymes, waterproofing agents, fabric comfort agents, shrink resistance agents, stretch resistance agents, stretch recovery agents, skin care agents, natural actives, antimicrobial actives, antiperspirant actives, cationic polymers, dyes, and combinations thereof, and preferably said benefit agents in the core of each of said microcapsules include fragrances.
6. an open cell content of 85% to 99%, preferably 90% to 98%, and / or an overall average pore size of 150 μm to 1000 μm, preferably 200 μm to 600 μm, and / or an average cell wall thickness of 5 μm to 200 μm, preferably 10 μm to 100 μm, more preferably 10 μm to 80 μm, and / or a final moisture content of from 0.5% to 25%, preferably from 1% to 20%, more preferably from 3% to 10%, based on the weight of the solid sheet article; and / or a thickness of 0.5 mm to 4 mm, preferably 0.6 mm to 3.5 mm, more preferably 0.7 mm to 3 mm, even more preferably 0.8 mm to 2 mm, and most preferably 1 mm to 2 mm; and / or 50 grams / m 2 ~500g / m 2 , preferably 150 g / m 2 ~450g / m 2 , more preferably 250 g / m 2 ~400g / m 2 and / or 0.05 grams / cm 3 ~0.5 grams / cm 3 , preferably 0.06 grams / cm 3 ~0.4 grams / cm 3 , more preferably 0.07 grams / cm 3 ~0.2 grams / cm 3 , and most preferably 0.08 grams / cm 3 ~0.15 grams / cm 3 and / or ・0.03m 2 / g to 0.25m 2 / g, preferably 0.04m 2 / g to 0.22 m 2 / g, more preferably 0.05m 2 / g to 0.2 m 2 / g, most preferably 0.1m 2 / g to 0.18m 2 The flexible porous dissolvable solid sheet article of any one of claims 3 to 5, characterized by a specific surface area of 100 / g.
7. A multi-layer structure comprising two or more layers of the flexible porous dissolvable solid sheet article of any one of claims 3 to 6.
Citation Information
Patent Citations
Fabric care conditioning composition in the form of an article
WO2011014643A1
WO2018/1411096A
Laundry detergent sheet with microcapsules
WO2018141096A1
Systems and methods for display binocular deformation compensation
WO2020014700A1
Process for making flexible, porous, dissolvable solid sheet articles with improved PORE structures
WO2020147000A1
